Ethylene-based copolymers and propylene-alpha-olefin-diene compositions for laminar articles

The problem of insufficient viscosity and green strength in hoses and conveyor belts by using a combination of propylene-α-olefin-diene (PEDM) terpolymer and ethylene-based copolymer is solved, significantly improving the performance of these materials.

CN116194528BActive Publication Date: 2025-03-07EXXONMOBIL CHEMICAL PATENTS INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180059364.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-23
Filing Date
2021-07-16
Publication Date
2025-03-07
Estimated Expiration
2041-07-16

AI Technical Summary

Technical Problem

Existing EP(D)M polymers lack sufficient viscosity and green strength when used in hoses and conveyor belts, resulting in poor processing and performance.

Method used

Elastomer compositions containing propylene-α-olefin-diene (PEDM) terpolymer and ethylene-based copolymer are used in combination with an appropriate amount of processing oil to improve the viscosity and green strength of the composition.

Benefits of technology

Improved green viscosities, aging viscosities, green strength, compression deformation, tensile and elongation are achieved, suitable for the preparation of high-quality automotive and industrial hoses and straps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004113657710000161
    Figure BDA0004113657710000161
  • Figure BDA0004113657710000162
    Figure BDA0004113657710000162
  • Figure BDA0004113657710000391
    Figure BDA0004113657710000391
Patent Text Reader

Abstract

An elastomeric composition suitable for use in layered articles such as hoses and belts may comprise: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene and having a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of an ethylene-based copolymer selected from: (a) a crystalline ethylene-based copolymer comprising 60 to 95 wt % ethylene, 0 to 10 wt % of one or more dienes, and 5 to 40 wt % C3 to C12 α-olefins, (b) an amorphous ethylene-based copolymer comprising 40 to 59 wt % ethylene, 0 to 10 wt % of one or more dienes, and 40 to 60 wt % C3 to C12 α-olefins, and (c) a combination of (a) and (b); and 10 to 200 phr of a process oil.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to USSN 63 / 055,665, filed on July 23, 2020, which is incorporated herein by reference. Technical Field

[0003] The present disclosure relates to elastomeric compositions suitable for use in hoses, belts, and other articles comprising ethylene-based copolymers and propylene-alpha-olefin-diene (PEDM) terpolymers. Background Art

[0004] Elastomeric polymer compounds, such as EP(D)M rubbers, are widely used in automotive and industrial applications (e.g., brake components, under-hood hoses, automotive radiator coolant hoses, air conditioning hoses, steam hoses, power transmission belts such as V-belts, flat belts, toothed or synchronous belts, multi-ribbed belts and conveyor belts) for their excellent thermal and oxidative stability, and their excellent chemical resistance to polar organic and aqueous inorganic fluids.

[0005] The properties required for automotive coolant, air and heater hose, air conditioning (A / C) and brake hose formulations include high green and tear strength, good retention of properties after aging balanced with low temperature flexibility and compression set, and easy mixing and processing. Belts, such as conveyor belts, have similar requirements. EP(D)M elastomers provide these properties and have been widely accepted as the reliable material of choice for a wide range of applications, such as general purpose hoses, heat resistant hoses, high heat resistant hoses, transmission belts, conveyor belts, etc.

[0006] One of the challenges in processing hose and strap compounds is having sufficient building tack, which is required to keep the rubber layer components adhered together during processing to prevent degradation prior to curing. That is, hoses and straps are multi-layer compounds with multiple metal and rubber layers that should adhere prior to curing. Tackifier resins (e.g., ESCOREZ TM ) have been used to improve build viscosity but generally result in limited improvements but lower green strength and physical properties after cure.

[0007] EP(D)M rubbers can be compounded to achieve a wide range of tensile strength and hardness. In addition to meeting typical requirements for mechanical properties such as heat resistance and compression set, coolant hose EP(D)M also offers good low-temperature sealing properties and electrochemical resistance.

[0008] In addition, the elastomeric hose body may include one or more elastomeric hose layers.Belt constructions typically include an elastomeric belt body, a helical or spirally wound tension cord or other textile tensile member embedded in the belt body, and other textile reinforcements typically embedded in the belt body or covering one or more of the belt surfaces.

[0009] The elastomeric hose body, or elastomeric belt body, may include one or more vulcanized rubber compositions, or elastomeric compositions, such as thermoplastic elastomer compositions. Elastomeric compositions traditionally include ethylene-propylene-(optionally diene) polymers, referred to as EP(D)M polymers or EP(D)M rubbers. Elastomeric compositions based on EP(D)M polymers need to have a suitable combination of processability and physical properties in both the vulcanized and unvulcanized states to meet manufacturing and end-use application requirements.

[0010] Examples of properties currently lacking in vulcanized EP(D)M compositions for hose or conveyor / belt applications are compression set, crosslink density, tack and green strength, particularly the balance between the two. Tack is the maximum force required to separate two identical composition samples (e.g., rubber specimens), while green strength is the tensile modulus measured at a certain degree of extension of a composition sample (e.g., rubber specimen), such as 25%. "Green" as used herein modifies the term and means uncured.

[0011] From a manufacturing perspective, for uncured EP(D)M compositions, the uncured elastomeric sheet coming out of the calender rolls should have sufficient tack to allow individual sheets to be spliced ​​to form a sheet several times wider than the width of the calendered sheet as it leaves the rolls. The uncured elastomer should also have sufficient green strength to be rolled onto a mandrel without sagging. However, it has been found that EP(D)M polymers have insufficient tack and possibly green strength for use as (making) hoses and conveyor / drive belts.

[0012] Viscosity and green strength are affected by the crystallinity of the polymer. Lower crystallinity results in greater viscosity. For example, the viscosity of an EP(D)M composition can be altered by reducing the ethylene content of the EP(D)M polymer and thereby reducing the crystallinity. However, lower crystallinity reduces green strength. In addition, lower crystallinity is detrimental to properties such as wear resistance, which is also an important property for hoses and conveyor / transmission belts. In fact, designing a single polymer (or polymer composition) with these distinct polymer characteristics to meet the viscosity and green strength requirements presents challenges in producing an acceptable polymer synthesis process.

[0013] Hydrocarbon tackifiers have been used as additives in EP(D)M compositions to enhance tack. However, non-hydrogenated tackifiers co-vulcanize with EP(D)M but do not exhibit long term heat resistance due, at least in part, to their unsaturation. Hydrogenated tackifiers exhibit better thermal stability. However, due to the lack of crosslinking with EP(D)M, they are more expensive and can be detrimental to cure and mechanical properties. Furthermore, tackifying resins increase the cost of EP(D)M compounds in the direction of when introduced as an additive rather than replacing the EP(D)M polymer component.

[0014] There is a need for polymers and polymer compositions having sufficient viscosity, green strength, compression set, tensile and elongation for use in hoses and conveyor / belts. In particular, there remains a need to improve the properties of hoses, such as heat resistance, compression set, extrusion, tensile and elongation. Summary of the invention SUMMARY OF THE INVENTION

[0016] The present disclosure relates to elastomeric compositions comprising ethylene-based copolymers and propylene-alpha-olefin-diene (PEDM) terpolymers for use in hoses, belts, and other articles comprising blends of such copolymers and terpolymers.

[0017] The present disclosure includes an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of an ethylene-based copolymer selected from: (a) comprising 60 to 95 wt % ethylene, 0 to 10 % by weight of one or more dienes and 5 to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 to 59 wt % ethylene, 0 to 10 wt % of one or more dienes and 40 to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer, and (c) the combination of (a) and (b); and 10 to 200 phr of process oil.

[0018] The present disclosure also includes a hose comprising: an inner rubber tube; a reinforcing fabric surrounding the inner rubber tube; and a rubber layer surrounding the reinforcing fabric; wherein the inner rubber tube and / or the rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of an ethylene-based copolymer; A polymer selected from the group consisting of: (a) a crystalline ethylene-based copolymer comprising 60 wt % to 95 wt % ethylene, 0 wt % to 10 wt % of one or more dienes, and 5 wt % to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes, and 40 wt % to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer, and (c) a combination of (a) and (b); and 10 phr to 200 phr of a process oil.

[0019] The present disclosure also includes a hose comprising: an inner rubber tube; a reinforcing fabric surrounding the inner rubber tube; and a rubber layer surrounding the reinforcing fabric; wherein the inner rubber tube and / or the rubber layer comprises an elastomeric composition comprising: 5 to 50 phr of PEDM, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 50 to 95 phr of an ethylene-based copolymer selected from: (a) comprising 60 to 95 wt % ethylene, 0 to 10 wt % of an ethylene-based copolymer; % to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes and 40 wt % to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer, and (c) the combination of (a) and (b); and 10 phr to 200 phr of process oil.

[0020] The present disclosure also includes a belt comprising: a first outer rubber layer; a second outer rubber layer; and a reinforcing fabric between the first and second outer rubber layers; wherein the first outer rubber layer and / or the second outer rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of a base % to 10 wt % of one or more dienes and 40 wt % to 60 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, and (c) a combination of (a) and (b); and 10 phr to 200 phr of a process oil.

[0021] The present disclosure also includes a belt comprising: a first outer rubber layer; a second outer rubber layer; and a reinforcing fabric between the first and second outer rubber layers; wherein the first outer rubber layer and / or the second outer rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of a terpolymer comprising 60 to 95 wt % ethylene, 0 to 10 wt % ethylene, % to 10 wt % of one or more dienes and 40 wt % to 60 wt % C3 to C12 α-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer; 0 phr to 75 phr of an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes and 40 wt % to 60 wt % C3 to C12 α-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer; and 10 phr to 30 phr of a process oil.

[0022] The present disclosure also includes a belt comprising: a first outer rubber layer; a second outer rubber layer; and a rubber skim layer between the first and second outer rubber layers. and a reinforcing fabric; wherein the first outer rubber layer and / or the second outer rubber layer and / or the rubber skin layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 to 90 MU; 20 to 95 phr of a crystalline ethylene-based copolymer comprising 60 to 95 wt % ethylene, 0 to 10 wt % of one or more dienes, and 5 to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer; 0 to 75 phr of an amorphous ethylene-based copolymer comprising 40 to 59 wt % ethylene, 0 to 10 wt % of one or more dienes, and 40 to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer; and 10 to 30 phr of a process oil. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The following figures are included to illustrate certain aspects of the embodiments and should not be considered to be exclusive embodiments. As will occur to those skilled in the art upon reading this disclosure, the disclosed subject matter is capable of numerous modifications, alterations, combinations, and equivalents in form and function.

[0025] Figure 1 is a partial perspective view of a drive belt according to some embodiments of the present disclosure.

[0026] Figure 2 is a partial perspective view of a drive belt according to another embodiment of the present disclosure.

[0027] Figure 3 is a partial perspective view of a drive belt according to yet another embodiment of the present disclosure.

[0028] Figure 4 An exemplary conveyor belt construction is shown including, in order, (a) a cover rubber layer, (b) alternating layers of fabric and rubber skins, and (c) a bottom rubber layer 408 .

[0029] Figure 5 An exemplary hose construction is shown, which includes, in sequence, (a) an inner rubber tube, (b) a reinforcing fabric, and (c) an outer rubber layer. DETAILED DESCRIPTION OF THE INVENTION

[0031] Embodiments of the present disclosure include elastomeric compositions (e.g., for belts and / or hoses) comprising a PEDM terpolymer (e.g., 5 to 80 phr of the composition), an ethylene-based copolymer (e.g., 20 to 95 phr), and a process oil (e.g., 10 to 200 phr). The ethylene-based copolymer can be a crystalline ethylene-based copolymer, an amorphous ethylene-based copolymer, or a combination thereof. Advantageously, such compositions provide improved green viscosity, viscosity after aging, green strength, compression set, stretching, and elongation. Due to these improved properties, the compositions described herein can be used to prepare higher quality automotive and industrial hoses and belts (e.g., power transmission belts and conveyor belts). In addition, the elastomeric compositions described herein can be more easily extruded, which can further improve the physical properties of the resulting hoses and belts because there are fewer defects, bubbles, and voids.

[0032] For example, a preferred elastomeric composition for belts (e.g., conveyor belts, drive belts, etc.) may include 5 to 80 phr of a propylene-α-olefin-diene (PEDM) terpolymer comprising 55 to 95 wt% propylene, 2.5 to 40 wt% α-olefin, and 0.05 to 25 wt% diene, the wt% being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a 125°C Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of a propylene-α-olefin-diene (PEDM) terpolymer comprising 60 to 95 wt% propylene, 2.5 to 40 wt% α-olefin, and 0.05 to 25 wt% diene, the wt% being based on the weight of the PEDM terpolymer; % ethylene, 0 wt % to 10 wt % of one or more dienes, and 5 wt % to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer; 0 phr to 75 phr of an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes, and 40 wt % to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer; and 10 phr to 30 phr of a process oil.

[0033] In another example, a preferred elastomeric composition for a hose may comprise 5 to 50 phr of a propylene-α-olefin-diene (PEDM) terpolymer comprising 55 to 95 wt% propylene, 2.5 to 40 wt% α-olefin, and 0.05 to 25 wt% diene, the wt% being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 50 to 95 phr of an ethylene-based copolymer selected from: (a) comprising 60 to 95 wt% ethylene; % to 10 wt % of one or more dienes and 40 wt % to 60 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes and 40 wt % to 60 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer, and (c) the combination of (a) and (b); and 10 phr to 200 phr of process oil.

[0034] definition

[0035] The term "copolymer" as used herein refers to a polymer including two or more monomers. The term "polymer" as used herein includes, but is not limited to, homopolymers, copolymers, terpolymers, etc. and their alloys and blends. The term "terpolymer" as used herein refers to a polymer synthesized from three different monomers. In some embodiments, the terpolymer can be prepared as follows: (1) all three monomers are mixed at the same time or (2) different comonomers are introduced sequentially. The mixing of comonomers can be carried out in one, two or possibly three different reactors in series and / or parallel. The term "polymer" as used herein also includes impact, block, grafted, random and alternating and gradient copolymers. The term "polymer" should also include components of all possible geometric shapes, unless otherwise specifically stated. Such configurations can include isotactic, syndiotactic and random (i.e., atactic) symmetric.

[0036] The term "blend" as used herein refers to a mixture of two or more polymers. The blend can be prepared, for example, by solution blending, melt mixing, or compounding in a shear mixer. Solution blending is commonly used to prepare adhesive formulations comprising baled butyl rubber, tackifiers, and oils. The solution blend is then applied to a fabric substrate and the solvent evaporated to leave the adhesive.

[0037] As used herein, the term "monomer" or "comonomer" can refer to the monomer used to form the polymer (i.e., the unreacted chemical in its prior form to polymerization) and can also refer to the monomer after it has been incorporated into the polymer (also referred to herein as a "[monomer]-derived unit"). Various monomers are discussed herein, propylene monomers, ethylene monomers, and diene monomers.

[0038] The term "ethylene-based copolymer" as used herein includes copolymers derived from ethylene, alpha-olefins containing 3 or more carbon atoms (e.g., 3-12 carbon atoms or 6-10 carbon atoms), and optionally, dienes. In a preferred embodiment, the ethylene-based copolymer is an ethylene-propylene copolymer or an ethylene-propylene-diene polymer.

[0039] As used herein, "ethylene-propylene-diene polymer" (EP(D)M) is defined as a copolymer having an ethylene content (derived from ethylene monomers) and a propylene content (derived from propylene monomers) and, optionally, a diene content (derived from diene monomers, preferably non-conjugated diene monomers). The ethylene content can be from 40 wt% to 95 wt% (e.g., from 41 wt% to 95 wt%, such as from 45 wt% to 90 wt%, such as from 50 wt% to 80 wt%), the diene content is from 0 wt% to 10 wt%, and the remainder (i.e., the remaining weight % of the polymer) is primarily (e.g., allowing for small amounts of impurities) or entirely propylene content, based on the weight of the polymer. The EP(D)M can have a Mooney viscosity, (ML, 1+4@125°C) of 15 to 100 (measured according to ASTM D1646-17). The terms "EP(D)M" and "EPDM" are used interchangeably and have the same meaning, unless the context dictates otherwise (e.g., when the polymer is referred to as finally comprising diene monomer(s)).

[0040] As used herein, the term "propylene-α-olefin-diene terpolymer" includes polymers derived from propylene, α-olefin (preferably ethylene) and diene monomers. Propylene-α-olefin-diene terpolymers may be referred to as PEDMs for short, even if α-olefins are considered as comonomers in such terpolymers instead of or in addition to ethylene, and / or polyenes are considered as replacements or in addition to the diene.

[0041] As used herein, "phr" means parts per 100 parts of rubber, where "rubber" is the total rubber content of the composition. Herein, both PEDM and ethylene-based copolymers (e.g., EP(D)M) are considered to contribute to the total rubber content, so that in a composition in which both are present, the "total rubber" is the total weight of the PEDM and ethylene-based copolymers. Thus, for example, a composition having 30 parts by weight of PEDM and 70 parts by weight of ethylene-based copolymers can be referred to as having 30 phr PEDM and 70 phr ethylene-based copolymers. Other components added to the composition are calculated based on phr. For example, adding 50 phr of oil to the composition means that for every 100 g of PEDM and ethylene-based copolymer combined, 50 g of oil is present in the composition. Unless otherwise specified, phr should be taken as phr by weight.

[0042] As used herein, "tensile strength" refers to the amount of stress applied to a sample to cause the sample to break. It can be expressed in Pascals or pounds per square inch (PSI). ASTM D412-16 can be used to determine the tensile strength of a polymer.

[0043] As used herein, "Mooney viscosity" is the Mooney viscosity of a polymer or polymer composition. The polymer composition analyzed for the determination of the Mooney viscosity should be substantially free of solvent. For example, the sample can be placed on a boiling water steam table in a hood to evaporate most of the solvent and unreacted monomers, and then dried overnight (12 hours, 90°C) in a vacuum oven according to laboratory analytical techniques before testing, or the test sample can be obtained from the devolatilized polymer (i.e., the polymer after devolatilization in an industrial scale process). Unless otherwise stated, the Mooney viscosity is measured using a Mooney viscometer according to ASTM D1646-17, but the following modifications / clarifications are made to the procedure. First, the sample polymer is pressed between two hot plates of a compression molding press before testing. The plate temperature is 125°C + / - 10°C instead of 50°C + / - 5°C recommended in ASTM D1646-17, because 50°C does not cause sufficient densification. In addition, although ASTM D1646-17 allows some options for die protection, if the two options provide conflicting results, PET 36 microns should be used as die protection. Additionally, ASTM D1646-17 does not indicate sample weight in paragraph 8; therefore, to the extent that results may vary based on sample weight, the Mooney viscosity determined in paragraph 8 of ASTM D1646-17 using a sample weight of 21.5 + / - 2.7 g will be used as the standard. Finally, the remaining procedures given in paragraph 8 of D1646-17 prior to testing are 30 minutes at 23 + / - 3°C in air; the Mooney values ​​reported herein are determined after 30 minutes of standing in air at 24 + / - 3°C. The samples are placed on either side of the spindle according to the ASTM D1646-17 test method; the torque required to turn the viscometer spindle at 2 rpm is measured by the sensor that determines the Mooney viscosity. Results are reported as Mooney units (ML, 1+4@125°C), where M is the Mooney viscosity number, L represents the large rotor (defined as ML in ASTM D1646-17), 1 is the warm-up time (in minutes), 4 is the sample run time after the motor is started (in minutes), and 125°C is the test temperature. Thus, a Mooney viscosity of 90 measured by the method described above would be reported as a Mooney viscosity of 90MU (ML, 1+4@125°C). Alternatively, the Mooney viscosity may be reported as 90MU; in such cases, unless otherwise stated, it should be considered that such viscosity was measured using the method just described. In some cases, a lower test temperature (e.g., 100°C) may be used, in which case the Mooney is reported as Mooney viscosity (ML, 1+4@100°C), or @T°C, where T is the test temperature.

[0044] Numerical ranges used herein include the values ​​recited in the range. For example, a numerical range of "1 wt % to 10 wt %" includes 1 wt % and 10 wt % within the range.

[0045] Room temperature is 23°C unless otherwise stated.

[0046] Elastomer composition

[0047] The elastomeric composition described herein comprises: 5 to 80 parts by weight phr of a PEDM terpolymer comprising 55 to 95 weight percent propylene, 2.5 to 40 weight percent α-olefin, and 0.05 to 25 weight percent diene, the weight percent being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of an ethylene-based copolymer; and 10 to 200 phr of a process oil. The ethylene-based copolymer may be: (a) a crystalline ethylene-based copolymer comprising 60 to 95 wt% ethylene, 0 to 10 wt% of one or more dienes, and 5 to 40 wt% of C3 to C12 alpha-olefins, the wt% being based on the total weight of the crystalline ethylene-based copolymer, and (b) an amorphous ethylene-based copolymer comprising 40 to 59 wt% ethylene, 0 to 10 wt% of one or more dienes, and 40 to 60 wt% of C3 to C12 alpha-olefins, the wt% being based on the total weight of the amorphous ethylene-based copolymer. Herein, the rubber portion (phr from which it is obtained) is cumulatively the PEDM terpolymer, the crystalline ethylene-based copolymer, and the amorphous ethylene-based copolymer.

[0048] PEDM can be present in the elastomeric composition at 5 to 80 phr, or 5 to 40 phr, or 10 to 30 phr, or 20 to 50 phr, or 30 to 70 phr, or 40 to 80 phr, or 45 to 80 phr, or 50 to 80 phr. For example, in a belt composition, PEDM can be present in the elastomeric composition at 5 to 80 phr, or 5 to 40 phr, or 10 to 30 phr, or 20 to 50 phr, or 30 to 70 phr, or 40 to 80 phr, or 45 to 80 phr, or 50 to 80 phr. In the hose composition, the PEDM may be present in the elastomeric composition at 5 phr to 50 phr, or 5 phr to 20 phr, or 10 phr to 30 phr, or 20 phr to 50 phr. The PEDM composition is further described below.

[0049] The ethylene-based copolymer (crystalline, amorphous, or mixtures thereof) can be present in the elastomeric composition at 20 to 95 phr, or 60 to 95 phr, or 70 to 90 phr, or 50 to 80 phr, or 30 to 70 phr, or 20 to 60 phr, or 20 to 55 phr, or 20 to 50 phr. Crystalline ethylene-based copolymer compositions and amorphous ethylene-based copolymer compositions are further described below.

[0050] For example, in the belt composition, the ethylene-based copolymer may be a crystalline ethylene-based copolymer or a mixture of a crystalline ethylene-based copolymer and an amorphous ethylene-based copolymer. In the belt composition, the crystalline ethylene-based copolymer may be present in the elastomeric composition at 20 to 95 phr, or 60 to 95 phr, or 70 to 90 phr, or 50 to 80 phr, or 30 to 70 phr, or 20 to 60 phr, or 20 to 55 phr, or 20 to 50 phr, and the amorphous ethylene-based copolymer may be present in the elastomeric composition at 0 to 75 phr, or 0 phr (i.e., absent), or 1 to 10 phr, or 5 to 25 phr, or 20 to 50 phr, or 30 to 65 phr, or 50 to 75 phr.

[0051] For example, in the hose composition, the ethylene-based copolymer can be a crystalline ethylene-based copolymer, an amorphous ethylene-based copolymer, or a mixture of a crystalline ethylene-based copolymer and an amorphous ethylene-based copolymer. In the hose composition, the ethylene-based copolymer (crystalline, amorphous, or a mixture thereof) can be present in the elastomeric composition at 50 phr to 95 phr, or 50 phr to 75 phr, or 60 phr to 90 phr, or 75 phr to 95 phr. In the hose composition, the crystalline ethylene-based copolymer may be present in the elastomeric composition at 0 phr to 75 phr, or 0 phr (i.e., not present), or 1 phr to 10 phr, or 5 phr to 25 phr, or 20 phr to 50 phr, or 40 phr to 75 phr, or 70 phr to 95 phr, and the amorphous ethylene-based copolymer may be present in the elastomeric composition at 0 phr to 75 phr, or 0 phr (i.e., not present), or 1 phr to 10 phr, or 5 phr to 25 phr, or 20 phr to 50 phr, or 40 phr to 75 phr, or 70 phr to 95 phr.

[0052] The processing oil may be present in the elastomeric composition at 10 to 200 phr, or 10 to 30 phr, or 30 to 75 phr, or 50 to 100 phr, or 75 to 150 phr, or 100 to 200 phr. Depending on the end-use application or product, the amount of processing oil in the elastomeric composition may vary. For example, when the end-use application or product is a belt (e.g., a transmission belt or a conveyor belt), the processing oil may preferably be present in the elastomeric composition at 10 to 30 phr, or 10 to 15 phr, or 10 to 20 phr, or 15 to 30 phr. In another example, when the end-use application or product is a hose (e.g., an automotive hose), the process oil may preferably be present in the elastomeric composition at 10 phr to 200 phr, or 10 phr to 30 phr, or 30 phr to 75 phr, or 50 phr to 100 phr, or 75 phr to 150 phr, or 100 phr to 200 phr.

[0053] Process oils, such as paraffinic and / or isoparaffinic process oils (examples include SUNPAR TM 2280 (available from HollyFrontier Refining & Marketing LLC); and IPOL TM 2300 (available from GP Petroleum Limited); and FLEXON TM 876、CORE TM 600 base oil, FLEXON TM 815 and CORE TM 2500 base oil (each available from ExxonMobil Chemical Company). In embodiments where the color of the final product may be important, white oils (e.g., API Group II or API Group III base oils) may be used as process oils. Examples include paraffinic and / or isoparaffinic oils having low (less than 1 wt %, e.g., less than 0.1 wt %) aromatic and heteroatom contents. The compositions of the present disclosure may contain 1 to 150 phr, e.g., 50 to 100 phr, e.g., 60 to 80 phr of process oil, or for sponge grades, 50 to 200 phr, e.g., 70 to 150 phr, e.g., 80 to 100 phr, and preferred process oils have a viscosity at 40° C. of 80 to 600 cSt.

[0054] The elastomer composition described herein may further include additives, which may include, but are not limited to, curing agents, crosslinking agents, fillers, plasticizers, compatibilizers, crosslinking agents, etc. and any combination thereof. Additives are further described below.

[0055] PEDM terpolymer

[0056] The PEDM terpolymers of the present disclosure have a polyene (preferably diene) content of 0.005 to 25 wt%, a C2 or C4 to C12 α-olefin (preferably ethylene) content of 2.5 to 40 wt%, and a propylene content of 55 to 95 wt%, the wt% being based on the weight of the PEDM terpolymer.

[0057] The compositions described herein may comprise a single PEDM terpolymer or a mixture of two or more PEDM terpolymers (eg, a dual reactor product).

[0058] The PEDM terpolymers of the present disclosure contain 50 wt % to 97 wt % propylene, based on the weight of the PEDM terpolymer. Other preferred ranges of propylene content include 55 wt % to 95 wt %, such as 65 wt % to 95 wt %, such as 75 wt % to 95 wt %, such as 85 wt % to 95 wt %, based on the weight of the PEDM terpolymer.

[0059] The PEDM terpolymers of the present disclosure include 2.5 wt % to 40 wt % C2 or C4 to C12 alpha-olefin comonomers (preferably ethylene), based on the weight of the PEDM terpolymer. Other preferred ranges of alpha-olefin (e.g., ethylene) content include 2.5 wt % to 30 wt %, such as 2.5 wt % to 20 wt %, such as 2.5 wt % to 15 wt %, such as 2.5 wt % to 10 wt %, or 10 wt % to 30 wt %, such as 15 wt % to 25 wt %, based on the weight of the PEDM terpolymer. C2 or C4 to C12 alpha-olefin comonomers include, but are not limited to, ethylene, butene, pentene, hexene, heptene, octene, nonene, decene, undecene, dodecene, and branched isomers thereof. Ethylene is particularly preferred.

[0060] The PEDM terpolymers of the present disclosure contain a polyene content (preferably a diene content) of 0.005 wt % to 25 wt %, such as 0.5 wt % to 20 wt %, such as 1 wt % to 15 wt %, such as 1.5 wt % to 10 wt %, such as 2.5 wt % to 7.5 wt %, based on the weight of the PEDM terpolymer. In at least one embodiment, the diene is a 5-ethylidene-2-norbornene content in an amount of 0.005 wt % to 25 wt %, such as 0.5 wt % to 20 wt %, such as 1 wt % to 15 wt %, such as 1.5 wt % to 10 wt %, such as 2.5 wt % to 7.5 wt %, based on the weight of the PEDM terpolymer. As indicated, the polyene is preferably (but not necessarily) a diene. Suitable dienes can be conjugated or non-conjugated. Preferably, the diene is non-conjugated. Dienes include, but are not limited to, 5-ethylidene-2-norbornene (ENB); 1,4-hexadiene; 5-methylene-2-norbornene (MNB); 1,6-octadiene; 5-methyl-1,4-hexadiene; 3,7-dimethyl-1,6-octadiene; 1,3-cyclopentadiene; 1,4-cyclohexadiene; vinyl norbornene (VNB); dicyclopentadiene (DCPD) and combinations thereof. Preferably, the diene is ENB or VNB.

[0061] Molecular weights (number average molecular weight (Mn), weight average molecular weight (Mw) and z-average molecular weight (Mz)) can be determined using a Polymer Laboratories Model 220 high temperature gel permeation chromatography size exclusion chromatography (GPC-SEC) equipped with an online differential refractive index (DRI), light scattering (LS) and viscometer (VIS) detector. Three Polymer Laboratories PLgel 10m Mixed-B columns were used for separation, with a flow rate of 0.54 ml / min and a nominal injection volume of 300 μL. The detector and column were contained in an oven maintained at 135°C. The material flow discharged from the SEC column was directed to a miniDAWN (Wyatt Technology, Inc.) optical flow cell and then to the DRI detector. The viscometer was in the SEC oven, arranged after the DRI detector. Details of these detectors and their calibration have been described, for example, by T. Sun, P. Brant, RR Chance and WW Graessley in Macromolecules, Vol. 34, No. 19, pp. 6812-6820 (2001).

[0062] The solvent for SEC experiments can be prepared by dissolving 6 grams of butylated hydroxytoluene (BHT) as an antioxidant in 4-liters of Aldrich reagent grade 1,2,4-trichlorobenzene (TCB). The TCB mixture is then filtered through a 0.7 micron glass pre-filter and subsequently through a 0.1 micron Teflon filter. The TCB is then degassed with an online degasser before entering the SEC. The polymer solution is prepared by placing the dry polymer in a glass container, adding the required amount of BHT-stabilized TCB, and then heating the mixture at 160°C while continuously stirring for about 2 hours. All quantities are measured gravimetrically. The TCB density used to express polymer concentration in mass / volume units can be 1.463 g / ml at 22°C and 1.324 g / ml at 135°C. The injection concentration can be from 1 mg / mL to 2 mg / mL, with lower concentrations used for higher molecular weight samples. The DRI detector and syringe should be purged before running each sample. The flow rate in the device can then be increased to 0.5 mL / min and the DRI allowed to stabilize for 8 to 9 hours before injecting the first sample. The concentration (c) of each point in the chromatogram is calculated from the baseline-subtracted DRI signal (I DRI )calculate:

[0063] c=K DRI I DRI / (dn / dc)

[0064] Where K DRI is a constant determined by calibrating the DRI with a series of monodisperse polystyrene standards with molecular weights ranging from 600 to 10 M, and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=690 nm is n=1.500. For the purposes of this disclosure and the claims thereto, for ethylene-propylene copolymers, (dn / dc)=0.1048, for EPDM containing ENB as the diene, (dn / dc)=0.1048-0.0016ENB, where ENB is the ENB content (in weight %) in the ethylene-propylene-diene terpolymer. In the case where other non-conjugated polyenes are used instead of ENB (or in addition to ENB), the value of ENB is taken as the weight percentage of the total non-conjugated polyenes. The value (dn / dc) for other polymers and copolymers (including PEDM terpolymers) is taken as 0.1. The units of parameters used throughout the description of this SEC method are as follows: Concentration is in g / cm 3 The molecular weight is expressed in g / mol and the intrinsic viscosity is expressed in dL / g.

[0065] The light scattering (LS) detector can be, for example, a high temperature miniDAWN (Wyatt Technology, Inc.). The main components are an optical flow cell, a 30 mW, 690 nm laser diode light source, and a series of three photodiodes placed at collection angles of 45°, 90°, and 135°. The polymer molecular weight M at each point in the chromatogram is determined by analyzing the LS output using the Zimm model of static light scattering (MB Huglin, Light Scattering from Polymer Solutions, Academic Press, 1971):

[0066]

[0067] Here, ΔR(θ) is the excess Rayleigh scattering intensity measured at a scattering angle θ, c is the polymer concentration determined by DRI analysis, A2 is the second virial coefficient (for the purposes of this disclosure, A2=0.0015 for ethylene homopolymers and A2=0.0015-0.00001EE for ethylene-propylene copolymers, where EE is the ethylene content in wt. % in the ethylene-propylene copolymer, P(θ) is the shape factor of the monodisperse random coils, and Ko is the optical constant of the system:

[0068]

[0069] Where N A is Avogadro's number and (dn / dc) is the refractive index increment of the system. The refractive index of TCB at 145°C and λ=690 nm is n=1.500.

[0070] The PEDM terpolymer of the present disclosure may have an Mw of 120,000 g / mol to 320,000 g / mol, such as 120,000 g / mol to 200,000 g / mol, such as 175,000 g / mol to 250,000 g / mol, such as 225,000 g / mol to 320,000 g / mol. The PEDM terpolymer may have an Mn of 50,000 g / mol to 150,000 g / mol, such as 50,000 g / mol to 100,000 g / mol, such as 75,000 g / mol to 125,000 g / mol, such as 100,000 g / mol to 150,000 g / mol. The PEDM terpolymer may have an Mz of 175,000 g / mol to 500,000 g / mol, such as 175,000 g / mol to 250,000 g / mol, such as 225,000 g / mol to 350,000 g / mol, such as 350,000 g / mol to 500,000 g / mol. For purposes of this application, in the event that DRI and LS measurements conflict, the LS measurement should be used for Mw and Mz, and the DRI measurement should be used for Mn.

[0071] The polydispersity index (Mw / Mn) of the PEDM terpolymer of the present disclosure may be from 2.0 to 2.7, such as from 2.0 to 2.5, or from 2.4 to 2.7.

[0072] In at least one embodiment, the PEDM terpolymer has an Mn of 50,000 to 150,000 g / mol; an Mw of 120,000 to 320,000 g / mol; and a polydispersity index of 2.0 to 2.7.

[0073] The PEDM terpolymer of the present disclosure may have a strength of 0.75 g / cm 3 Up to 0.95g / cm 3 , for example 0.80g / cm 3 Up to 0.92g / cm 3 , for example 0.85g / cm 3 Up to 0.90g / cm 3 The density of the composite is as measured according to ASTM D1505-10 test method.

[0074] The PEDM terpolymer of the present disclosure may have a melt flow rate (MFR, 2.16 kg weight, 230° C.) measured according to ASTM D1238-13 equal to or greater than 0.5 g / 10 min. For example, the MFR (2.16 kg, at 230° C.) of the PEDM terpolymer of the present disclosure may be 0.5 g / 10 min to 15 g / 10 min, such as 1 g / 10 min to 12.5 g / 10 min, such as 1.5 g / 10 min to 10 g / 10 min, such as 2.5 g / 10 min to 8 g / 10 min, or 5 g / 10 min to 7.5 g / 10 min.

[0075] The PEDM terpolymers of the present disclosure may have a Mooney viscosity (ML, 1+4@125°C) of 5MU to 90MU, or 5MU to 25MU, or 20MU to 50MU, or 40MU to 60MU, or 50MU to 80MU, or 60MU to 90MU.

[0076] Differential scanning calorimetry (DSC) is used to determine the Tg of alpha-olefin-ethylene-diene polymer according to ASTM D3418-03. Melting temperature (Tm) and heat of fusion (Hf) are also determined by DSC. DSC data can be obtained using TA Instruments model Q200 machine. A sample weighing about 5 mg to 10 mg can be kept in an aluminum sample pan and hermetically sealed. The sample can be gradually heated to 200 ° C at a rate of 10 ° C / minute, and then kept at 200 ° C for 2 minutes. Subsequently, the sample can be cooled to -90 ° C at a rate of 10 ° C / minute and isothermally kept at -90 ° C for 2 minutes. This can be followed by a second heating cycle, in which the sample can be heated to 200 ° C at 10 ° C / minute. The first and second cycle thermal events can be recorded.

[0077] During the second heating cycle, the appearance of melting indicates crystallinity and the heat of fusion so measured is used to calculate crystallinity. The exotherm (recorded as the area under the sample melting peak) is a measure of the heat of fusion and can be expressed in joules per gram of polymer. The melting point is recorded as the maximum endothermic temperature within the melting range of the sample relative to the baseline measurement of the temperature-dependent incremental heat capacity of the polymer.

[0078] The PEDM terpolymers of the present disclosure may have a heat of fusion (Hf) of less than 1 J / g. Additionally or alternatively, the PEDM terpolymers of the present disclosure may have a heat of fusion (Hf) of less than 15 J / g. Additionally or alternatively, the PEDM terpolymers of the present disclosure may have a heat of fusion (Hf) of 15 J / g or greater. In at least one embodiment, the PEDM terpolymer is amorphous. Additionally or alternatively, the PEDM terpolymer may have atactic propylene sequences. In at least one embodiment, the PEDM terpolymer has a glass transition temperature (Tg) of -45°C to -2°C, or -35°C to -30°C. In at least one embodiment, the PEDM terpolymer may have a Hf of less than 1 J / g and syndiotactic r diads, wherein the percentage of r diads is low enough to still be substantially amorphous (i.e., having a low H f ).

[0079] The PEDM terpolymers of the present disclosure may have atactic polypropylene sequences. Additionally or alternatively, the PEDM terpolymers of the present disclosure may be amorphous, meaning that the PEDM terpolymers will not exhibit a melting peak when subjected to a differential scanning calorimetry (DSC) test. Alternatively, the PEDMs according to some embodiments may display minor melting peaks such that they may be observed to have Hf<1 J / g according to the DSC method described herein. Additionally, when the PEDM displays any melting peak, such peak may be a single peak, or the PEDM may display secondary melting peaks adjacent to the primary peak. For purposes of this article, these secondary melting peaks are collectively considered a single melting point, wherein the highest peak among these peaks (relative to the baseline described herein) is considered to be the melting point of the PEDM terpolymer.

[0080] According to yet another embodiment, the crystallinity of the PEDM terpolymer may be expressed in terms of a percentage of crystallinity (i.e., % crystallinity), as determined according to the DSC procedure described herein. While the PEDM according to certain embodiments is amorphous (and may therefore be said to have 0% crystallinity), if the PEDM according to various other embodiments exhibits any crystallinity, it preferably has a % crystallinity of 0.1% to 5%, preferably 0.1% to 3%. (Crystallinity is determined by dividing (i) the measured heat of fusion by (ii) the heat of fusion of 100% crystalline polyethylene, which has a value of 293 J / g (B. Wunderlich, Thermal Analysis, Academic Press, 1990, pp. 417-431)).

[0081] The percent crystallinity was calculated using the formula: [area under the curve (in J / g) / H° (in J / g)]×100, where H° is the ideal heat of fusion for a perfect crystal of a homopolymer of the major monomer component. These values ​​for H° were obtained from Polymer Handbook, Fourth Edition, published by John Wiley and Sons, New York 1999, except that a value of 290 J / g was used for H° (polyethylene), a value of 140 J / g for H° (polybutylene), and a value of 207 J / g (H°) for H° (polypropylene).

[0082] Additionally, as described above, when a sample exhibits no melting peaks, as in the case of amorphous polymers, it can be said to have no Hf. However, for example, even some amorphous or nearly amorphous PEDM samples may exhibit minor melting peaks, such that the Hf on the first melt may be observed to be <1 J / g. Therefore, for the purposes of this application, a PEDM may be considered amorphous when it has a Hf <1 J / g, or when it exhibits no discernible melting peak.

[0083] Ethylene-based copolymers

[0084] The composition of the present disclosure comprises an ethylene-based copolymer. The ethylene-based copolymer can be one or more crystalline ethylene-based copolymers, one or more amorphous ethylene-based copolymers, or a combination of one or more crystalline ethylene-based copolymers and one or more amorphous ethylene-based copolymers.

[0085] Unless otherwise specified, the term "ethylene-based copolymer" can be a crystalline ethylene-based copolymer, an amorphous ethylene-based copolymer, or both a crystalline ethylene-based copolymer and an amorphous ethylene-based copolymer. As described below, crystalline versus amorphous is based on the heat of fusion (Hf) of the ethylene-based copolymer, which depends at least in part on the ethylene content in the ethylene-based copolymer.

[0086] The crystalline ethylene-based copolymer can have an ethylene content of 60 wt % to 95 wt %, or 60 wt % to 80 wt %, or 75 wt % to 95 wt %, based on the weight of the crystalline ethylene-based copolymer. The amorphous ethylene-based copolymer can have an ethylene content of 40 wt % to 59 wt %, or 40 wt % to 55 wt %, or 45 wt % to 59 wt %, based on the weight of the amorphous ethylene-based copolymer.

[0087] The remainder of the composition of the crystalline ethylene-based copolymer and the amorphous ethylene-based copolymer is C3 to C12 alpha-olefin and optionally, a polyene (preferably a diene).

[0088] Thus, the crystalline ethylene-based copolymer can have an ethylene content of 60 wt % to 95 wt % (or 60 wt % to 80 wt %, or 75 wt % to 95 wt %); a C3 to C12 α-olefin content of 5 wt % to 40 wt % (or 5 wt % to 25 wt %, or 20 wt % to 40 wt %); and a diene content of 0 wt % to 10 wt % (or 0 wt % to 5 wt %, or 1 wt % to 5 wt %, or 5 wt % to 10 wt %). In addition, the amorphous ethylene-based copolymer can have an ethylene content of 40 wt% to 60 wt% (or 40 wt% to 55 wt%, or 45 wt% to 60 wt%); a C3 to C12 α-olefin content of 40 wt% to 60 wt% (or 45 wt% to 60 wt%, or 40 wt% to 55 wt%); and a diene content of 0 wt% to 10 wt% (or 0 wt% to 5 wt%, or 1 wt% to 5 wt%, or 5 wt% to 10 wt%).

[0089] C3 to C12 alpha-olefins include propylene, butene, pentylene, hexene, heptene, octene, nonene, decene, undecene, dodecene and their branched isomers. Propylene is particularly preferred according to some embodiments (e.g., so that the ethylene-based copolymer can be an EP(D)M copolymer), while butene (1-butene) is preferred in still other embodiments (e.g., so that the ethylene-based copolymer can be an EB(D)M copolymer). In addition, in certain embodiments, the ethylene-based copolymer of the present disclosure can have an isotactic polypropylene content.

[0090] Any polyene suitable in PEDM is suitable for inclusion in ethylene-based copolymers, wherein VNB or ENB are preferred, especially ENB. According to other embodiments, suitable polyenes may include conjugated dienes. Conjugated dienes include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-di(C1-C5 alkyl)-1,3-butadiene, such as 2,3-dimethyl-1,3-butadiene, 2,3-diethyl-1,3-butadiene, 2-methyl-3-ethyl-1,3-butadiene or 2-methyl-3-isopropyl-1,3-butadiene, aryl-1,3-butadiene, 1,3-pentadiene or 2,4-hexadiene. Dienes also include vinyl aromatic compounds: styrene, o-, m- or p-methylstyrene, "vinyl toluene" commercial mixtures, p-(tert-butyl)styrene, methoxystyrene, chlorostyrene, vinyl mesitylene, divinylbenzene or vinyl naphthalene.

[0091] The crystalline ethylene copolymer may have a Hf of 15 J / g or more, or from 15 J / g to 45 J / g, or from 15 J / g to 30 J / g, or from 20 J / g to 40 J / g, or from 30 J / g to 45 J / g.

[0092] The amorphous ethylene copolymer may have a Hf of 0 J / g to 14 J / g, or 0 J / g to 5 J / g, or 3 J / g to 10 J / g, or 7 J / g to 14 J / g.

[0093] The ethylene copolymer may have a Mooney viscosity (ML, 1+4@125°C) of 20MU to 90MU, or 20MU to 50MU, or 40MU to 60MU, or 50MU to 80MU, or 60MU to 90MU.

[0094] The ethylene-based copolymer may be an ethylene-propylene copolymer, in particular an EP(D)M terpolymer (e.g., VISTALON ® available from ExxonMobil). TM 7001, VISTALON available from ExxonMobil TM 7500, VISTALON available from ExxonMobil TM 6602, VISTALON available from ExxonMobil TM 2502, TAFMER available from Mitsui Chemicals TM , or VERSIFY available from Dow Chemical TM ) or EB(D)M terpolymers. The ethylene-based copolymers of the present disclosure may have a weight average molecular weight (Mw) of 10,000 g / mol to 400,000 g / mol, or 100,000 g / mol to 200,000. The ethylene-based copolymers may also or alternatively have a melting point (DSC) of less than 110° C. or less than 100° C.

[0095] The compositions described herein may comprise a single ethylene-based copolymer or a mixture of two or more ethylene-based copolymers. In addition, the ethylene-based copolymers may be used in combination with any type of thermoplastic polymer and / or synthetic elastomer other than the ethylene-based copolymers.

[0096] Polymer blending

[0097] The compositions of the present disclosure can be formed by combining PEDM and ethylene-based copolymers using any suitable method known in the field of polymer processing. For example, the composition can be prepared by blending PEDM and ethylene-based copolymers in solution and generally removing the blend. This polymer composition has a predetermined amount of PEDM and ethylene-based copolymers and can be prepared by independent polymerization of the first and second elastomeric polymer components. This separate polymerization can be carried out in a series or parallel polymerization reactor or in a single polymerization reactor with at least two different polymerization catalysts. The recovery procedure of this predetermined composition is described in U.S. Patent No. 4,722,971, which is incorporated herein by reference. The present disclosure includes traditional Ziegler-Natta catalyst systems, however, metallocene catalyst systems are also considered by the present disclosure.

[0098] In at least one embodiment, the method for preparing a composition of PEDM and ethylene-based copolymers includes contacting a first metallocene catalyst with ethylene, propylene and a diene in a first reactor to form the PEDM. The method further includes contacting a second metallocene catalyst with ethylene and propylene and optionally a diene in a second reactor (or first reactor) to form an ethylene-based copolymer, and so on for other ethylene-based copolymers. The method may include transferring the PEDM to the second reactor or transferring the ethylene-based copolymer to the first reactor, and recovering the mixture of the PEDM and the ethylene-based copolymer from the second reactor or the first reactor, respectively. The recovered polymer composition may then be crosslinked, for example, as described in more detail below.

[0099] Alternatively, in at least one embodiment, the blend can be prepared by combining and mixing the PEDM and the ethylene-based copolymer from their respective reactions, for example, in a production extruder, such as an extruder on an injection molding machine or on a continuous extrusion line.

[0100] In at least one embodiment, the polymers may be blended in a batch mixer such as a BANBURY TM or BARBENDER TM The polymer melt is blended in a mixer. Blending can include blending PEDM and ethylene-based copolymer melts in an extruder, such as a single screw extruder or a twin screw extruder. Suitable examples of extrusion techniques for polymer blends can be described in more detail in PLASTICS EXTRUSION TECHNOLOGY, F. Hensen, Ed. (Hanser, 1988), pp. 26-37 and POLYPROPYLENE HANDBOOK, EP Moore, Jr. Ed. (Hanser, 1996), pp. 304-348, which are incorporated herein by reference.

[0101] PEDM and ethylene-based copolymers may also be blended by a combination of methods including, but not limited to, solution blending, melt mixing, compounding in a shear mixer, and combinations thereof. For example, dry blending followed by melt blending in an extruder, or batch mixing of some components followed by melt blending with other components in an extruder. A double cone blender, a belt blender, or other suitable blender may also be used, or in a Farrel continuous mixer (FCM). TM ) PEDM and ethylene-based copolymers are blended.

[0102] The PEDM and ethylene-based copolymers and optional additives (eg, curatives, crosslinkers, fillers, plasticizers, compatibilizers, crosslinkers, etc.) can be blended in different orders, which in some cases can alter the properties of the resulting composition.

[0103] In some cases, a masterbatch comprising PEDM, an ethylene-based copolymer, and additives (except a curative and a crosslinking agent) can be prepared at a first temperature. Then, a curative and / or a crosslinking agent can be mixed into the masterbatch at a second temperature lower than the first temperature.

[0104] In some embodiments, the masterbatch can be prepared by mixing the PEDM and ethylene-based copolymers and additives (except the curing agent and cross-linking agent) together in one step until the additives are incorporated (e.g., a homogenous blend is produced). This is referred to herein as a first pass method or first pass blending. After the first pass blending produces the masterbatch, the curing agent and / or cross-linking agent can be mixed into the masterbatch to produce the final blend.

[0105] In alternative embodiments, a two-step mixing method can be used to prepare a masterbatch. For example, in some embodiments, a masterbatch can be prepared by mixing an ethylene-based copolymer (crystalline, amorphous, or a blend of the two) with additives (except curing agents and cross-linking agents) until the additives are incorporated into the ethylene-based copolymer (e.g., to produce a uniform blend). The resulting blend is then mixed with PEDM and a curing agent and / or a cross-linking agent. This method is referred to herein as a second pass method or a second pass blending. Alternatively, a curing agent and / or a cross-linking agent can be mixed into the masterbatch after adding PEDM in the second pass to produce a final blend.

[0106] In some second-pass blending embodiments, mixing the ethylene-based copolymer / additive (except curatives and cross-linking agents) blend with PEDM can be performed in a mixer or other suitable system without removing the ethylene-based copolymer / additive blend from the mixer (i.e., first-pass blending) to produce a masterbatch. In alternative embodiments, the ethylene-based copolymer / additive (except curatives and cross-linking agents) blend can be removed from the mixer or other suitable system for producing the blend and then mixed with PEDM in a mixer or other suitable system (i.e., second-pass blending) to produce a masterbatch.

[0107] A homogeneous mixture can be achieved by mixing for a certain time, which corresponds to producing a homogeneous mixture. In some cases, the mixing parameters of the ethylene-based copolymer and the selected additive can be changed when a homogeneous mixture is obtained. For example, when carbon black (an exemplary filler) is mixed with an ethylene-based copolymer, the torque can reach a maximum steady state, where a minimum torque increase is observed to no significant torque increase.

[0108] Composition

[0109] The compositions of the present disclosure include and / or are the reaction products of a curing agent with the above-mentioned PEDM and ethylene-based copolymers (as polymer blends or otherwise) (and in any form: pellets, bundles or otherwise). As described above, the compositions of the present disclosure may further include and / or be the reaction products of a curing agent with one or more additives (e.g., fillers, plasticizers, compatibilizers, cross-linking agents, etc.).

[0110] In embodiments where a curative (e.g., a crosslinking agent or a vulcanizing agent) is present in the composition, the polymers of the composition may be present in at least partially crosslinked form (i.e., at least a portion of the polymer chains are crosslinked to each other, e.g., as a result of a typical curing process for EP(D)M rubbers). Accordingly, particular embodiments provide at least partially crosslinked elastomeric compositions prepared by mixing (according to any of the methods described above for polymer blends) a composition comprising: (a) PEDM and an ethylene-based copolymer; (b) one or more vulcanization activators; (c) one or more vulcanizing agents; and / or (d) one or more other additives.

[0111] Suitable vulcanization activators include zinc oxide, stearic acid, etc. These activators can be mixed in an amount of 0.1phr to 20phr. Different vulcanization activators can be present in different amounts. For example, when the vulcanization activator includes zinc oxide, zinc oxide can be present in an amount of 1phr to 20phr, such as 2.5phr to 10phr, such as about 5phr, and stearic acid can be preferably used in an amount of 0.1phr to 5phr, such as 0.1phr to 2phr, such as about 1.5phr.

[0112] Any suitable vulcanizing agent may be used. Of particular note are the curing agents described in U.S. Pat. No. 7,915,354 at column 19, line 35 to column 20, line 30, which description is hereby incorporated by reference (e.g., sulfur, peroxide-based curing agents (VULCUP® available from Arkema of Colombes, France) and TM 40KE), resin curing agents, silane and hydrosilane curing agents). Other examples include phenolic resin curing agents (e.g., described in U.S. Pat. No. 5,750,625, also incorporated herein by reference). Curing aids (e.g., zinc dimethacrylate (ZDMA) (DYMALINK TM 708, available from Cray Valley) or those described in the already incorporated description of U.S. Patent No. 7,915,354).

[0113] The further additives may be selected from any known additives useful in EP(D)M compositions and may include in particular one or more of the following:

[0114] Vulcanization accelerators: The compositions of the present disclosure may contain 0.1 to 15 phr, or 1 to 5 phr, or 2 to 4 phr, where examples include thiazoles such as 2-mercaptobenzothiazole or mercaptobenzothiazole disulfide (MBTS); guanidines such as diphenylguanidine; sulfenamides such as N-cyclohexylbenzothiazolesulfenamide; dithiocarbamates such as zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc dibenzyldithiocarbamate (ZBEC); and zinc dibutyldithiocarbamate, thioureas such as 1,3-diethylthiourea, thiophosphates, and the like;

[0115] Processing aids (e.g., polyethylene glycol or zinc soap);

[0116] Carbon black (e.g., having a particle size of 20 nm to 600 nm and a structure having a DBPA (dibutyl phthalate absorption value) of 0 to 150 measured by the DBP method). The composition of the present disclosure may contain 1 phr to 500 phr, preferably 1 phr to 200 phr, or 50 phr to 150 phr of carbon black;

[0117] Inorganic fillers (talc, calcium carbonate, clay, silica, aluminum trihydrate, etc.), which may be present in the composition at 1 to 200 phr, preferably 20 to 100 phr, or 30 to 60 phr;

[0118] When foaming may be desired, sponge or foam grade additives, such as blowing agents or foaming agents, especially in very high Mooney viscosity embodiments, such as those suitable for sponge grades. Examples of such agents include: azodicarbonamide (ADC), o-benzenesulfonyl hydrazide (OBSH), p-toluenesulfonyl hydrazide (TSH), 5-phenyltetrazole (5-PT) and sodium bicarbonate in citric acid. Microcapsules may also or instead be used for such foaming applications. These may include heat-expandable microspheres comprising a polymer shell containing a propellant. Suitable examples are described in U.S. Patent Nos. 6,582,633 and 3,615,972, WIPO Publication Nos. WO 99 / 46320 and WO 99 / 43758, and the contents of these documents are hereby incorporated by reference. Examples of such heat-expandable microspheres include EXPANCEL commercially available from Akzo Nobel NV. TM Products and ADVANCELL available from Sekisui TM In other embodiments, sponging or foaming can be achieved by injecting gas and / or liquid (e.g., water, CO2, N2) directly into the rubber in an extruder so that foaming occurs after the composition passes through a die; and

[0119] Various other additives may also be included, such as antioxidants (e.g., 1,2-dihydro-2,2,4-trimethylquinoline), stabilizers, preservatives, UV absorbers, antistatic agents, slip agents, moisture absorbers (e.g., calcium oxide), pigments, dyes, or other colorants.

[0120] The elastomeric composition of the present disclosure may optionally comprise carbon black, for example, in an amount of 1 to 500 phr, for example, 5 to 250 phr, for example, 10 to 125 phr, for example, 50 phr.

[0121] The at least partially cross-linked polymer composition of the present disclosure may be prepared by any suitable means as described in the polymer blending section above (e.g., BANBURY TM The above components are mixed in a mixer (e.g., a mixer) to form. Mixing in these embodiments may include any one or more typical mixing methods for EP(D)M compositions, such as open mill mixing, mixing using an internal mixer or kneader, and extrusion (e.g., via a twin-screw extruder).

[0122] In addition, in some embodiments, additives can be incorporated into polymer blends directly or as a part of a masterbatch (i.e., an additive package containing several additives to be added at a predetermined ratio). Masterbatch can be added in any suitable amount. For example, a masterbatch comprising additives can be used in an amount of about 0.1 wt % to about 10 wt %, or about 0.25 wt % to about 7.5 wt %, or about 0.5 wt % to about 5 wt %, or about 1 wt % to about 5 wt %, or about 2 wt % to about 4 wt %, based on the gross weight of polymer blends and masterbatch. This is a common practice in polymer processing, and is generally used for adding pigments, additives, and fillers to the final composition. The dispersion (or "thinning") of the masterbatch can be carried out as a part of the process step for manufacturing articles, such as in an extruder on an injection molding machine or a continuous extrusion line, or during an independent compounding process.

[0123] The compositions described herein comprising PEDM and ethylene-based copolymers can have a green rubber-to-rubber tack force of 500 g-force / inch-width or greater, or from 500 g-force / inch-width to 2500 g-force / inch-width, or from 1000 g-force / inch-width to 5000 g-force / inch-width, or from 1500 g-force / inch-width to 5000 g-force / inch-width, or from 1250 g-force / inch-width to 4500 g-force / inch-width, or from 1500 g-force / inch-width to 4000 g-force / inch-width after blending. In addition, the compositions described herein comprising PEDM and ethylene-based copolymers can have an aged rubber-to-rubber tack force (1 month, room temperature) of 500 g-force / inch-width or greater, or from 500 g-force / inch-width to 2500 g-force / inch-width, or from 1000 g-force / inch-width to 6000 g-force / inch-width, or from 1500 g-force / inch-width to 5000 g-force / inch-width, or from 2000 g-force / inch-width to 5000 g-force / inch-width, or from 4000 g-force / inch-width to 6000 g-force / inch-width.

[0124] The compositions described herein comprising PEDM and ethylene-based copolymers can have a green rubber to rubber adhesion retention percentage from blending to aging at room temperature for 1 month (aged adhesion divided by blended adhesion times 100) of 50% to 250%, or 90% to 200%, or 100% to 250%, or 150% to 250%. For example, an adhesion retention of 200% means that the adhesion doubles with aging.

[0125] The rubber to rubber adhesion test can be measured based on a modified ASTM D3330 / D330M-04 (2010) Method F. Specifically, the following modifications to the ASTM method are utilized: (1) instead of a 2 μm finished stainless steel substrate according to the ASTM method, an uncured rubber sheet substrate of the rubber being tested is used; and (2) for conditioning, instead of 24 hours at 23° C. in the ASTM method, the samples are tested under ambient conditions. This method provides the benefits of a larger test range and longer dwell time, thereby providing a larger scale test of the samples for the Tel-Tak method.

[0126] The extrudability of the unvulcanized compound can be tested, evaluated and determined using standard test methods for rubber properties, and therefore via a screw-type extruder, such as a Garvey type, equipped with an ASTM extrusion die. At an extrusion rate of about 170 rpm or more, the composition comprising PEDM and ethylene-based copolymers described herein can have an extrusion output (g / min) of about 180 g / min or more, such as about 190 g / min or more, such as about 200 g / min or more. The Garvey die extrusion test can be measured based on the ASTM D2230 method.

[0127] The compositions described herein comprising PEDM and ethylene-based copolymers may have a green strength of 0.2 MPa to 0.9 MPa, such as 0.3 MPa to 0.8 MPa, such as 0.4 MPa to 0.7 MPa.

[0128] The compression set of a material is the permanent deformation retained after the compressive stress is released. Compression set is usually expressed as a percentage of the original specimen thickness of method A (constant force) or the percentage of the original deflection of method B (constant deflection). Compression set can be measured by ASTM D395-B method. In at least one embodiment, when the disclosed composition comprising PEDM and an ethylene-based copolymer is press-cured for 35 minutes at 180°C, the composition has a compression set (%) of 1% to 25%, such as 2% to 20%, such as 3% to 15%, such as 3% to 10%, such as 4% to 8%. In another embodiment, when the disclosed composition comprising PEDM and an ethylene-based copolymer is press-cured for 72 hours at ambient temperature, the composition has a compression set (%) of 1% to 50%, such as 2% to 40%, such as 3% to 30%. In another embodiment, when the disclosed composition comprising PEDM and an ethylene-based copolymer is press cured at a temperature of about 100° C. or greater for 72 hours, the composition has a compression set (%) of 40% to 95%, such as 45% to 80%, such as 50% to 75%.

[0129] The compression set of a material depends on the crosslink density of the material, which is defined as the torque difference between the maximum torque (also referred to as "MH") and the minimum torque (also referred to as "ML"). MH, ML and the torque difference "MH-ML" are evaluated by the moving die rheometer (MDR) test method (standard test method for rubber curing). MDR can be measured by ASTM D5289 method, usually reported in deciNewton meters (dN.m). The disclosed composition comprising PEDM and ethylene-based copolymers can have a crosslink density of 2 dN.m to 50 dN.m, such as 3 dN.m to 40 dN.m, such as 4 dN.m to 30 dN.m, such as 5 dN.m to 25 dN.m.

[0130] The disclosed compositions comprising PEDM and ethylene-based copolymers can have a tensile strength (MPa) of 4 to 150 MPa, such as 5 to 125 MPa, such as 5 to 100 MPa, such as 5 to 50 MPa, such as 5 to 25 MPa, such as 50 to 100 MPa.

[0131] Elongation at break is the percentage of elongation calculated by dividing the elongation at break by the initial gauge length and multiplying by 100. The elongation at break after oil aging can be measured by the ASTM D471 method. The disclosed composition comprising PEDM and an ethylene-based copolymer can have an elongation of 25% to 750%, such as 30% to 500%, such as 40% to 300% after oil aging. Alternatively, the disclosed composition comprising PEDM and an ethylene-based copolymer can have an elongation of 150% to 700%, such as 160% to 600%, such as 170% to 500% after oil aging. Alternatively, the disclosed composition comprising PEDM and an ethylene-based copolymer can have an elongation of 50% or more, such as 50% to 100%, such as 60% to 100%, such as 70% to 100%, such as 80% to 100% after oil aging. Oil aging can occur at 100°C or higher, such as 125°C or higher, such as 150°C or higher. In at least one embodiment, the disclosed composition comprising PEDM and an ethylene-based copolymer can have an elongation of 100% to 500%, such as 110% to 400%, such as 120% to 300% after oil aging at 150°C for 7 days, and thus after press curing at 180°C for 30 minutes. In another embodiment, the disclosed composition comprising PEDM and an ethylene-based copolymer can have an elongation of 100% to 500%, such as 110% to 400%, such as 120% to 300% after oil aging at 100°C for 24 hours.

[0132] End Use

[0133] The compositions of the present disclosure may be used as one or more components of a hose or belt (eg, a V-belt, a flat belt, a toothed or synchronous belt, a multi-ribbed belt, or a conveyor belt).

[0134] To form an elastomeric hose or belt body portion according to at least one embodiment of the present disclosure, the polymers may be blended according to a suitable mixing method and as described above with general rubber compounding ingredients, including but not limited to fillers, plasticizers, stabilizers, vulcanizers / curing agents, adjuvants and accelerators in conventionally employed amounts.

[0135] Figure 1 This is a partial perspective view of the transmission belt. Figure 1 As shown, the synchronous belt 100 includes an elastomeric main body 102 and a pulley contact portion 104 arranged along the inner edge of the main body 102. The main body 102 includes a composition comprising PEDM and an ethylene-based copolymer of the present disclosure. The pulley contact portion 104 is configured to form alternating transverse protrusions 106 and grooves 108, which are configured to couple with transverse groove wheels or sprockets. A tensile layer 110 is arranged in the main body 102 to provide support and strength for the belt 100. The tensile layer 110 includes a plurality of tensile cables 112 arranged longitudinally along the length of the main body 112. The cables 112 include any suitable material, such as one or more of cotton, rayon, polyamide, polyester, aramid, steel, glass, carbon, polyketone, basalt, boron or non-continuous fibers oriented for low load capacity. A reinforcing fabric 114 is arranged on the protrusions 106 and grooves 108 and forms a pulley contact portion. The reinforcing fabric 114 may have any suitable configuration such as a conventional textile consisting of warp and weft threads at an angle, or may include warp threads bonded together by spatial pick-up threads, or a knitted or woven configuration, or a nonwoven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, acrylic, aramid, polyketone, hemp, jute, or fiberglass.

[0136] Figure 2 This is a partial perspective view of the transmission belt. Figure 2As shown, the toothed V-belt 200 includes an elastomeric portion 202 and a tensile layer 204 including a cord 206. The body portion 202 includes a composition of the present disclosure including PEDM and an ethylene-based copolymer. The cord 206 includes any suitable material, such as one or more of cotton, rayon, polyamide, polyester, aramid, steel, glass, carbon, polyketone, basalt, boron, or non-continuous fibers oriented for low load capacity. The V-belt 200 includes a pulley contact portion 208 having two juxtaposed sides of the belt designed to be inserted into a V-shaped pulley. The V-belt 200 includes grooves 210 and protrusions 212. Included in the V-belt category are those V-belts designed for continuously variable transmission ("CVT") applications, which typically display a belt body that is relatively wider than the belt thickness.

[0137] Figure 3 This is a partial perspective view of the transmission belt. Figure 3 As shown, the multi-V-ribbed belt 300 includes a main body 302 and a tensile reinforcement member 304 including a cable 306. The main body 302 includes a composition of the present disclosure including PEDM and an ethylene-based copolymer. The longitudinal groove pulley contact portion 308 includes a plurality of protrusions 310 alternating with a plurality of grooves 312, which together define a drive surface 314 of the belt 300. Figure 1 , Figure 2 and Figure 3 In each of these examples, the corresponding pulley contact portion and the corresponding body portion can be coupled / coupled and can be formed of the same material or layered with different materials.

[0138] The conveyor belt can be manufactured as a layered composition of a calendered sheet of the present disclosure composition comprising PEDM and an ethylene-based copolymer and a reinforcing fabric. For example, Figure 4 An exemplary conveyor belt construction 400 is shown, which includes, in order, (a) a cover rubber layer 402, (b) alternating fabric 404 and rubber skin layers 406, and (c) a bottom rubber layer 408. Other layers may be included in other conveyor belt constructions. The cover rubber layer 402, the rubber skin layer 406, and / or the bottom rubber layer 408 include a composition of the present disclosure including PEDM and an ethylene-based copolymer.

[0139] The reinforcing fabric 404 may have any suitable configuration such as a conventional textile consisting of warp and weft threads at an angle, or may include warp threads bound together by space pick-up threads, or a knitted or woven configuration, or a nonwoven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, acrylic resin, aramid, polyketone, hemp, jute, or fiberglass.

[0140] The manufacture of conveyor belts is usually carried out by laminating the above layers (or other desired layer sequences) using a calendering process. The calendered layered structure is then cured. The high viscosity in the rubber layer improves the fusion between adjacent layers and reduces bubble formation between layers.

[0141] The hose can be manufactured as a layered composition by extruding the composition of the present disclosure comprising PEDM and an ethylene-based copolymer. Figure 5 An exemplary hose construction 500 is shown, which includes, in order, (a) an inner rubber tube 502, (b) a reinforcing fabric 504, and (c) an outer rubber layer 506. Other layers may be included in other hose constructions. The inner rubber tube 502 and / or the outer rubber layer 506 may include a composition comprising PEDM and an ethylene-based copolymer of the present disclosure.

[0142] The reinforcing fabric 504 may have any suitable configuration such as a conventional textile consisting of warp and weft threads at an angle, or may include warp threads bound together by space pick-up threads, or a knitted or woven configuration, or a nonwoven fabric. Suitable fabrics include one or more of cotton, polyester, polyamide, acrylic resin, aramid, polyketone, hemp, jute, or fiberglass.

[0143] Conveyor belts are typically manufactured by extruding an inner rubber tube 502, covering the inner rubber tube 502 with a reinforcing fabric 504, and extruding an outer rubber layer 506 onto the reinforcing fabric 504. High viscosity in the rubber layer improves fusion between adjacent layers and reduces bubble formation between layers.

[0144] Other machine-made products

[0145] The composition of the present disclosure can be used as one or more components of industrial and garden hoses, sponge parts and gaskets and seals for molding and extrusion. In such components, the composition of the present disclosure (comprising PEDM, based on ethylene copolymer, optionally, amorphous based on ethylene copolymer and optionally, one or more additives) can adhere to another polymer composition, the polymer composition includes cotton, rayon, polyamide, polyester, aromatic polyamide, steel, aluminum, glass, carbon, polyketone, basalt and boron, which can be in the form of including film, band, hose, tire, textile or nonwoven fabric separately. Due to the enhanced adhesion properties of the composition of the present disclosure, the adhesion of the aforementioned materials can be significantly better than the adhesion between EP (D) M and the material. For example, the adhesion between the film (substrate) of the composition with the present disclosure and the film of polyester or polyamide can have the rubber and substrate viscosity exceeding 20gm force / inch width. In addition, polyester or polyamide fiber can adhere to the composition of the present disclosure more firmly than independent EP (D) M.

[0146] Example Implementation

[0147] A first non-limiting example embodiment of the present disclosure is an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of an ethylene-based copolymer selected from: (a) comprising 60 to 95 wt % ethylene, 0 % to 10 wt % of a crystalline ethylene-based copolymer of one or more dienes and 5 wt % to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes and 40 wt % to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer, and (c) the combination of (a) and (b); and 10 phr to 200 phr of a process oil.The first non-limiting example embodiment may further include one or more of the following: Element 1: an elastomeric composition comprising: 5 to 50 phr of PEDM; 50 to 95 phr of an ethylene-based copolymer; and 10 to 200 phr of a process oil; Element 2: Element 1 and wherein the composition has a raw rubber to rubber adhesion of 500 g-force / inch width or greater; Element 3: Element 1 and wherein the composition has a raw rubber to rubber adhesion of 1000 to 5000 g-force / inch width; Element 4: Element 1 and wherein the composition has a raw rubber to rubber adhesion of 500 g-force / inch width or greater; Element 5: Element 1 and wherein the composition has a rubber-to-rubber adhesion of 1000 g force / inch width or more to 6000 g force / inch width after aging at room temperature for 1 month; Element 6: Element 1 and wherein the composition has a raw rubber-to-rubber adhesion retention percentage of 50% to 250% from blending to aging at room temperature for 1 month; Element 7: Element 1 and wherein the composition has a raw rubber-to-rubber adhesion retention percentage of 100% to 250% from blending to aging at room temperature for 1 month; Element 8: Elastomer composition , comprising: 5 to 80 phr of the PEDM terpolymer; 20 to 95 phr of the crystalline ethylene-based copolymer; 0 to 75 phr of the amorphous ethylene-based copolymer; and 10 to 30 phr of a process oil; Element 9: wherein the crystalline ethylene-based copolymer has a 125°C Mooney viscosity (ML (1+4)) of 20 MU to 90 MU; Element 10: wherein the crystalline ethylene-based copolymer has a Hf of 15 J / g or greater; Element 11: wherein the amorphous ethylene-based copolymer has a 125°C Mooney viscosity (ML (1+4)) of 20 MU to 90 MU Mooney viscosity (ML(1+4)); Element 12: wherein the amorphous ethylene-based copolymer has a Hf of 0 J / g to 14 J / g; Element 13: wherein the PEDM terpolymer has a number average molecular weight of 50,000 g / mol to 150,000 g / mol; Element 14: the PEDM terpolymer has a weight average molecular weight of 120,000 g / mol to 320,000 g / mol; Element 15: wherein the PEDM terpolymer has a polydispersity index of 2 to 2.7; and Element 16: the elastomeric composition further comprises 1 phr to 500 phr of carbon black. Examples of combinations include, but are not limited to, a combination of element 1 with two or more of elements 2-7; a combination of two or more of elements 9-16; one or more elements 9-16 combined with element 1 and optionally further combined with one or more of elements 2-7; and a combination of element 8 with one or more elements 9-16.

[0148] A second non-limiting example embodiment of the present disclosure is a hose comprising: an inner rubber tube; a reinforcing fabric surrounding the inner rubber tube; and a rubber layer surrounding the reinforcing fabric; wherein the inner rubber tube and / or the rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of a base % to 10 wt % of one or more dienes and 40 wt % to 60 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer, and (c) a combination of (a) and (b); and 10 phr to 200 phr of a process oil. The second non-limiting example may also include one or more of the following: element 1; element 2; element 3; element 4; element 5; element 6; element 7; element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; and element 17: wherein the reinforcing fabric is selected from the group consisting of: cotton, polyester, polyamide, acrylic resin, aramid, polyketone, hemp, jute, fiberglass, and any combination thereof. Examples of combinations include, but are not limited to: a combination of element 1 with two or more of elements 2-7; a combination of two or more of elements 9-16; one or more elements 9-16 combined with element 1 and optionally further combined with one or more of elements 2-8.

[0149] A third non-limiting example embodiment of the present disclosure is a hose comprising: an inner rubber tube; a reinforcing fabric surrounding the inner rubber tube; and a rubber layer surrounding the reinforcing fabric; wherein the inner rubber tube and / or the rubber layer comprises an elastomeric composition, the elastomeric composition comprising: 5 to 50 phr of PEDM, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 50 to 95 phr of an ethylene-based copolymer selected from: (a) comprising 60 to 95 wt % ethylene, 0 to 10 wt % ethylene, and 1 to 20 wt % ethylene. % by weight of one or more dienes and 5 to 40 wt% of a crystalline ethylene-based copolymer of C3 to C12 alpha-olefins, the wt% being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising 40 to 59 wt% ethylene, 0 to 10 wt% of one or more dienes and 40 to 60 wt% of a C3 to C12 alpha-olefin, the wt% being based on the total weight of the amorphous ethylene-based copolymer, and (c) a combination of (a) and (b); and 10 to 200 phr of process oil. The third non-limiting example may also include one or more of the following: element 2; element 3; element 4; element 5; element 6; element 7; element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; and element 17.

[0150] A fourth non-limiting example embodiment of the present disclosure is a belt comprising: a first outer rubber layer; a second outer rubber layer; and a reinforcing fabric between the first and second outer rubber layers; wherein the first outer rubber layer and / or the second outer rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer comprising 55 to 95 wt % propylene, 2.5 to 40 wt % α-olefin, and 0.05 to 25 wt % diene, the wt % being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML(1+4)) of 5 MU to 90 MU; 20 to 95 phr of ethylene-based copolymers selected from: (a) crystalline ethylene-based copolymers comprising 60 wt% to 95 wt% ethylene, 0 wt% to 10 wt% of one or more dienes, and 5 wt% to 40 wt% C3 to C12 alpha-olefins, the wt% being based on the total weight of the crystalline ethylene-based copolymers, (b) amorphous ethylene-based copolymers comprising 40 wt% to 59 wt% ethylene, 0 wt% to 10 wt% of one or more dienes, and 40 wt% to 60 wt% C3 to C12 alpha-olefins, the wt% being based on the total weight of the amorphous ethylene-based copolymers, and (c) a combination of (a) and (b); and 10 phr to 200 phr of process oil. The fourth non-limiting example may also include one or more of the following: element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; and element 17.

[0151] A fifth non-limiting example embodiment of the present disclosure is a belt comprising: a first outer rubber layer; a second outer rubber layer; and a reinforcing fabric between the first and second outer rubber layers; wherein the first outer rubber layer and / or the second outer rubber layer comprises an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of a 60 to 95 wt % ethylene, 0 wt % The invention also provides a crystalline ethylene-based copolymer of 0 to 10 wt % of one or more dienes and 5 to 40 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer; 0 to 75 phr of an amorphous ethylene-based copolymer containing 40 to 59 wt % of ethylene, 0 to 10 wt % of one or more dienes and 40 to 60 wt % of C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer; and 10 to 30 phr of a process oil. The fifth non-limiting example may also include one or more of the following: element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; and element 17.

[0152] A sixth non-limiting example embodiment of the present disclosure is a belt comprising: a first outer rubber layer; a second outer rubber layer; and alternating layers of rubber skin layers and reinforcing fabrics between the first and second outer rubber layers; wherein the first outer rubber layer and / or the second outer rubber layer and / or the rubber skin layers comprise an elastomeric composition comprising: 5 to 80 phr of a PEDM terpolymer, wherein the PEDM terpolymer has a Mooney viscosity (ML (1+4)) of 5 MU to 90 MU; 20 to 95 phr of a 60 to 95 wt % % ethylene, 0 wt % to 10 wt % of one or more dienes and 5 wt % to 40 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the crystalline ethylene-based copolymer; 0 phr to 75 phr of an amorphous ethylene-based copolymer containing 40 wt % to 59 wt % ethylene, 0 wt % to 10 wt % of one or more dienes and 40 wt % to 60 wt % C3 to C12 alpha-olefins, the wt % being based on the total weight of the amorphous ethylene-based copolymer; and 10 phr to 30 phr of process oil. The sixth non-limiting example may also include one or more of the following: element 9; element 10; element 11; element 12; element 13; element 14; element 15; element 16; and element 17.

[0153] Unless otherwise indicated, all numerical values ​​used in the specification and the appended claims to express the quantity of ingredients, properties such as molecular weight, reaction conditions, etc. should be understood in all cases as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters listed in the following specification and the appended claims are approximate values, which may vary depending on the desired properties sought to be obtained by the embodiments of the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in light of the number of reported significant digits and by applying ordinary rounding techniques.

[0154] One or more illustrative embodiments incorporating the invention embodiments disclosed herein are presented herein. For the sake of clarity, all features of physical implementation are not described or shown in this application. It should be understood that in the development of the physical implementation incorporating the invention embodiments, many execution-specific decisions must be made to realize the developer's goal, such as complying with system-related, business-related, government-related and other constraints, which depend on implementation and change from time to time. Although the efforts of the developers may be time-consuming, for those of ordinary skill in the art, this effort remains a routine task and benefits from the present disclosure.

[0155] Although compositions and methods are described herein in terms of "comprising" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps.

[0156] It should be understood that, although the invention has been described in conjunction with specific embodiments of the invention, the above description is intended to illustrate rather than limit the scope of the invention. Other aspects, advantages and improvements will be apparent to those skilled in the art to which the invention belongs.

[0157] In order to help better understand the embodiments of the present invention, the following examples of preferred or representative embodiments are given. The following examples should not be interpreted as limiting in any way, or defining the entire scope of the present invention. Example

[0158] Mooney viscosity (ML) can be measured by ASTM D1646-17 ((1+4), 125°C, 2s -1The melt flow rate (MFR) is measured at 230°C and 2.16kg load according to ASTM D1238 test method and is expressed as dg / min or g / 10min. Ethylene content is determined using FTIR according to ASTM D3900 and is not corrected for diene content. ENB is determined using FTIR according to ASTM D6047. Mooney scorch is measured according to ASTM D1646-17 test method. Moving die rheometer is measured according to ASTM D5289 test method. Tensile strength, elongation and green strength are measured according to ASTM D412 test method. Hardness is measured according to ASTM D2240 test method. Abrasion test is measured according to DIN 53516 test method. Tear strength is measured according to ASTM D624 test method. Compression deformation is measured according to ASTM D395-B test method. Die C tear strength is measured according to ASTM D624 test method. Tensile and elongation after oil aging are measured according to ASTM D471 test method. Garvey die extrusion and evaluation were performed based on ASTM D2230 test method.

[0159] Molecular weights (number average molecular weight (Mn), weight average molecular weight (Mw) and Z-average molecular weight (Mz)) were determined using a Polymer Laboratories Model 220 high temperature GPC-SEC equipped with an online differential refractive index (DRI), light scattering (LS) and viscometer (VIS) detector. It uses three Polymer Laboratories PLgel 10m Mixed-B columns for separation, using a flow rate of 0.54ml / min and a nominal injection volume of 300μL. The detector and column are contained in an oven maintained at 135°C. The material flow discharged from the SEC column is directed to a miniDAWN (Wyatt Technology, Inc.) optical flow cell and then to the DRI detector. The DRI detector is an integrated part of the Polymer Laboratories SEC. The viscometer is in the SEC oven, arranged after the DRI detector. Details of these detectors and their calibration have been described, for example, by T. Sun, P. Brant, RR Chance and WW Graessley in Macromolecules, Vol. 34, No. 19, pp. 6812-6820 (2001).

[0160] Table 1 shows the polymer properties of several PEDM polymers used to prepare the compounds of Examples 1 and 2. The EP(D)M polymer used was VISTALON TM7001, which is an ethylene-propylene copolymer having a Mooney viscosity (ML, 1+4@125°C) of 60 MU and an ethylene content of 73 wt%, and VISTALON TM 2502, which is an ethylene-propylene copolymer having a Mooney viscosity (ML, 1+4@125°C) of 26 MU and an ethylene content of 49 wt%. This elastomeric formulation was found to be suitable for use in, for example, hose applications.

[0161] Table 1. Polymer composition

[0162]

[0163] Example 1. Compositions containing EP(D)M polymer, carbon black, oil and curing agent were prepared in BANBURY TM Mixer or Farrel BANBURY TM The mixture was prepared in a mixer (model OOC) with a volume of 1.57 or 4.3 L, respectively. Table 2 shows a representative composition. Mixing was used to compound using a fill factor of 70%. At the beginning of mixing, the polymer, carbon black and additives were introduced at a speed of 50 rpm. The impact was increased three times during the mixing cycle. Mixing was continued for 5 minutes, at which time the batch was discharged. The temperature of the discharged batch averaged about 250°F. About 5 grams of the compound masterbatch was isolated for rheological measurements.

[0164] Table 2 shows the peroxide cured EP(D)M hose formulations used in this study. The control formulation contained VISTALON TM 7500EP(D)M. The polymer content is 100phr, which includes VISTALON TM 7500 control polymer and PEDM. That is, VISTALON TM A portion of the 7500EP(D)M is replaced by PEDM polymer at a level of 10 or 20 phr. ESCOREZ TM 5600 was added to one formulation at 5 phr as a comparative example. A masterbatch formulation excluding the curing agent was prepared in the first pass as described in Table 2. The average batch discharge temperature from the mixer was about 300°F. The curing agent was added in the second pass to complete the compound. The compounds used in all tests were prepared by Farrel BANBURY TM OOC mixer preparations, except those compounds for Garvey die extrusion, were prepared by BANBURY TM Mixer Preparation.

[0165] In Tables 2 and 3, "Polymer" refers to the corresponding amount of EP(D)M plus PEDM polymer as in Examples E1-E8 contained in the composition; Carbon Black N550 is carbon black (available in pellet form from Cabot); SUNPAR TM 2280 is paraffin processing oil; AGERITE TM Resin D TM is an antioxidant 1,2-dihydro-2,2,4-trimethylquinoline (available from Vanderbilt Chemicals); EGDMA is a vulcanizing / crosslinking agent; and VULCUP TM 40KE is an organic peroxide curing / crosslinking agent. The composition is considered to be a useful composition for EP(D)M compounds and is therefore considered useful for the processability of Test Examples E1.1-E1.8 compared to Comparative Examples C1.1 and C1.2. The oil content in all formulations (E1.1-E1.8) is 45 phr.

[0166] Table 2. Blend composition and conditions

[0167]

[0168] *For C2 formulation, 5 phr of ESCOREZ was added in the first pass TM 5600.

[0169] The curing agent was added to the masterbatch in the second pass. The batch was passed through the mill several times to ensure uniform dispersion of the curing agent. The batch containing the curing agent was then cured in an electric hot press and tested for various physical and mechanical properties.

[0170] The rubber to rubber adhesion test was conducted based on a modified ASTM D3330 / D330M-04 (2010) Method B and F. Specifically, the following modifications to the ASTM method were used: (1) instead of a 2 μm finished stainless steel substrate according to the ASTM method, an uncured rubber sheet substrate of the same rubber being tested was used; and (2) for conditioning, instead of 24 hours at 23° C. in the ASTM method, the samples were tested under ambient conditions. This approach provides the benefits of a larger test range and longer dwell time, thereby providing a larger scale test of the samples for the Tel-Tak method.

[0171] Table 3 includes the mechanical properties of various compounds, which can be green samples or cured samples as described in the table. Table 3 includes green bonding properties, green strength, crosslink density and compression set of different examples after initial compounding and again after aging at 150°C for 7 days and at 100°C for 24 hours.

[0172]

[0173]

[0174] At the green stage, all of the PEDM-based compounds of the present invention (E1.1-E1.8) show improvements in build viscosity relative to the control compound (C1.1), which is also higher than the build viscosity of the control compound (C1.2). Compounds containing PEDM-3 (E1.5 and E1.6) show the highest viscosity improvement, but the green strength is comparable to the control compound (C1.1), while the green strength of the control compound (C1.2) is lower than the green strength of the control compound (C1.1). In general, at a loading level of 10 phr PEDM, the PEDM compounds (PEDM 1-4) show green strength comparable to the control compound (C1.1). Compounds containing PEDM-3 show high viscosity improvements when compared to compounds that do not include the formulation. There is generally a trade-off between the build viscosity and green strength of a compound. Compounds with a good balance of building viscosity and green strength as shown in the present disclosure are certainly beneficial for processing. Compared to the control compound (C1.1), the PEDM-based compounds (E1.1-E1.8) show comparable or moderately lower green tear strength, but generally better cured tear strength. The PEDM-based compounds (E1.1-E1.8) also show better compression set than the control compound (C1.1) (e.g., about 25% improvement for E1.5 and E1.8). Compared to the control compound (C1.1), the PEDM-based compounds (E1.1-E1.8) show a moderate increase in tensile strength, but maintain it well after heating. Compared to the control compound (C1.1), the PEDM-based compounds (E1.1-E1.8) also show comparable elongation, but generally better retention. After oil aging, the PEDM based compounds (E1.1-E1.8) show better retention of tensile strength and elongation than the control compounds (C1.1) and (C1.2).

[0175] Table 4 shows the Garvey die extrusion performance of PEDM-based compounds (E1.1-E1.8). PEDM-based compounds (E1.2, E1.6 and E1.8) show higher extrusion output at higher extrusion rates than the control compound (C1.1) without loss of profile appearance. The compound containing PEDM-1 (E1.2) shows the highest extrusion output at the highest extrusion rate without loss of profile appearance. Thus, improved extrusion output is also observed when PEDM is added.

[0176] Table 4. Garvey die extrusion performance

[0177]

[0178] Example 2. The following example is to use EP(D)M polymer to crystallize VISTALON by adding the PEDM polymer listed in Table 1. TM 7001 and amorphous VISTALON TM EP(D)M based compounds prepared with 2502. Crystalline VISTALON TM 7001 is an ethylene-propylene copolymer with a Mooney viscosity (ML, 1+4@125°C) of 60MU and an ethylene content of 73% by weight, amorphous VISTALON TM 2502 is an ethylene-propylene copolymer with a Mooney viscosity (ML, 1+4@125°C) of 26 MU and an ethylene content of 49 wt%. This elastomeric formulation is found to be suitable for conveyor belt applications, for example. PEDM is used in place of amorphous VISTALON in the compounds of the present invention. TM 2502. Two types of tackifiers ESCOREZ TM 5600 and ESCOREZ TM 5400 was also used in the comparative examples. TM 5600 and ESCOREZ TM 5400 are all DCPD-based compounds, among which ESCOREZ TM 5400 is hydrogenated, and ESCOREZ TM 5600 has 10% aroma. ESCOREZ TM 5600 and ESCOREZ TM The softening point of 5400 is about 100°C. Both PEDM and tackifiers were also used to produce PEDM-based compounds (E5-E6) to evaluate the two tackifying materials ESCOREZ TM 5600 and ESCOREZ TM In general, EP(D)M compounds with PEDM showed significant improvements in build viscosity over the control, which was higher than the ESCOREZ TM By using PEDM and ESCOREZ together TM The resin improves the balance of build tack and physical strength. Table 5 shows the peroxide cured EP(D)M delivery machine formulations. The control formulation includes crystalline VISTALON TM 7001 and amorphous VISTALON TM 2502. The polymer content is 100 phr, which includes VISTALON TM 7001 and VISTALON TM2502EP(D)M control polymer and PEDM; i.e., VISTALON TM A portion of 2502EP(D)M was replaced by PEDM polymer at a level of 20 phr. TM 5600 and ESCOREZ TM 5400 was added at 5 phr to two formulations as comparative examples (C2.2-C2.3). Compounding was performed in a 1.8 liter intermeshing mixer. The batch was taken out at 156°C (max). The curing agent was mixed on an open mill for about 8 minutes.

[0179] The compound was cured at 160°C for 8 minutes using compression molding. The ML and Mooney scorch properties of the compound were determined according to the ASTM D1646 method. MRD was measured by the ASTM D5289 method. Hardness was measured by the ASTM D2240 method. Tensile and elongation after oil aging were measured according to the ASTM D471 test method. Tear strength was measured by the ASTM D624 method. Heat aging was performed at 150°C for 168 hours. Picma viscosity is a measure of the viscosity between two surfaces. Typically, two unvulcanized calendered rubber sheets are kept in contact for a specified time under a constant load. The force required to pull the sheet apart is measured as viscosity. Unless otherwise specified, the two layers of uncured rubber are the same composition. Here, a Picma viscosity tester, PI type (purchased from Toyoseiki), is used, with a measurement range of 0.1N to 15N and a step length of 0.1N. The sheet is prepared by roller milling at 80°C, and the roller gap is adjusted to obtain a sheet of 2.0mm±0.1mm. The first sheet is fixed to a cylindrical weight sample holder, and the sample in contact with the first sheet is the second sheet. The contact time is 30 seconds, the stretching rate is 25 mm / min, and the applied deadweight is 500 grams of force (4.9 N). The measurement is carried out at 23°C. Abrasion resistance is measured by DIN 53516 method.

[0180] Table 5. Formulations

[0181]

[0182] Table 6 shows the build tack, cure, mechanical and aging properties of the inventive compounds (E1-E6) and comparative control compounds (C2.1-C2.3).

[0183] In the comparison between PEDM-based compounds (E2.1-E2.4) and control compounds (C2.1-C2.3), PEDM-based compounds (E2.1-E2.4) showed better performance than ESCOREZ-based compounds. TMThe compounds (C2.2-C2.3) of the present invention have a higher build viscosity improvement over the control compound (C2.1). After curing, the PEDM-based compounds (E2.1-E2.4) show higher hardness, but lower elongation and tear strength than the control compound (C2.2-C2.3). The PEDM-based compounds (E2.1-E2.4) show better wear resistance than the control compound (C2.2-C2.3), while the PEDM-based compounds (E2.2-E2.4) show wear resistance comparable to the control compound (C2.2-C2.3). The PEDM-based compounds (E2.1-E2.4) show better tensile retention than the control compound (C2.1), which is consistent with the control compound (C2.2-C2.3).

[0184] Add PEDM and ESCOREZ TM In the case of PEDM-based compounds (E2.5) and (E2.6), the PEDM and ESCOREZ TM For example, compared with the control compound (C2.2-C2.3) (ESCOREZ only TM ) and PEDM-based compound (E2.1) (PEDM only), PEDM-based compounds (E2.5-E2.6) show comparable (or closer) build tack than PEDM-based compound (E2.1), and comparable elongation to control compound (C2.2) (comparison E2.5). The abrasion resistance of PEDM-based compounds (E2.5-E2.6) is between the abrasion resistance of PEDM-based compound (E2.1) and control compounds (C2.2) and (C3), which is comparable to the abrasion resistance of control compound (C2.1). In general, aromatic ESCOREZ TM The PEDM-based compound (E2.5) of 5600 showed a higher yield than that containing hydrogenated ESCOREZ TM The PEDM-based compound (E2.6) with 5400 exhibited a better balance of physical strength and viscosity than the control compound containing only ESCOREZ TM The ML of the PEDM-based compounds (E2.5-E2.6) is the lowest among the tested compounds, as observed in Table 6, which would lead to easier processing. Therefore, the use of PEDM and ESCOREZ together in the compounding TM It is an agent that can produce advantages over the use of one or the other agent alone.

[0185]

[0186]

[0187] Example 3. The following examples (E3.1-E3.8) of the present disclosure demonstrate that 50 phr of PEDM can impart improved tack and processing to EP(D)M based compounds without significantly degrading mechanical properties (before and after aging) and cure properties.

[0188] PEDM polymers with different ethylene contents (5% to 15%) and different ENB levels (2% to 10%) were added at 50 phr (replacing VISTALON TM 2502) was added to the EP(D)M formulation. The results show that the viscosity is improved due to the addition of PEDM polymer. The lower Mooney viscosity and enhanced viscosity will reduce the possibility of layer separation, which provides advantages in terms of conveyor belt processing and potential overall performance.

[0189] The polymer properties of the PEDM and EP(D)M polymers used in this study are shown in Table 7. Melting temperature (Tm) and heat of fusion (Hf) were determined by differential scanning calorimetry (DSC) using commercially available equipment such as the Perkin Elmer Pyris 1 thermal analysis system. Typically, 10 mg to 15 mg of a sample that had been stored at room temperature for at least 48 hours was sealed in an aluminum pan and loaded into the instrument at room temperature. The sample was heated to 170°C and equilibrated at 170°C for 3 minutes, then cooled to -70°C at 10°C / min, then equilibrated at -70°C for 3 minutes, and then heated to 170°C at a heating rate of 10°C / min. T was calculated from the second heating cycle. m and H f The value of .

[0190] Table 7. Properties of PEDM polymers

[0191]

[0192] In Table 8, the corresponding amounts of EP(D)M plus PEDM polymer are as shown in Examples E3.1-E3.4. During the compounding period of the formulation, the masterbatch (without curing agent) was mixed on a laboratory scale 1.8 liter intermeshing mixer. The batch was passed through the mixer at a maximum of 156°C. A conventional mixing method was used, with the mixer fill factor maintained at 75%. The curing agent was mixed on an open mill for about 8 minutes.

[0193] Table 8. Blend composition and conditions

[0194]

[0195] The compound properties of the uncured compounds are shown in Table 9. The compound viscosities of the PEDM based compounds (E3.1, E3.2 and E3.4) were found to be lower than those of the compounds containing VISTALONTM 2502, which has potential advantages in terms of processing on extruders and calendars. Likewise, due to the lower compound Mooney viscosity, the PEDM-based compounds (E3.1, E3.2 and E3.4) have slightly higher scorch times at 125°C than the control compound (C1), and thus can have higher scorch safety during processing. The PEDM-based compound (E3.3) shows a higher Mooney viscosity and lower scorch time than the control compound (C3.1) and the PEDM-based compounds (E3.1, E3.2 and E3.4), which is due to the higher MI of PEDM-3 than VISTALON TM 2502 and PEDM-1, PEDM-4 and PEDM-2. Therefore, PEDM can be used as a blending partner with crystalline EP(D)M grades in sulfur-cured formulations to improve processing.

[0196] Table 9. Compound properties

[0197]

[0198] Table 10 shows the moving die rheometer of PEDM-based compounds (E3.1, E3.2, E3.3 and E3.4). For PEDM-based compounds (E3.1, E3.2, E3.3 and E3.4), the MDR values ​​show a slight decrease in MH-ML values, which may come from their lower ENB% content and / or ethylene content. In addition, the cure times (ts2 and tc90) of PEDM-based compounds (E3.1, E3.2, E3.3 and E3.4) are similar to those containing VISTALON TM The cure time of the control compound (C3.1) with 2502 was comparable. In addition, the t90 of the PEDM-based compound (E3.4) was lower than the t90 of the PEDM-based compounds (E3.1, E3.2, and E3.3) due to the higher ENB% content of PEDM-2.

[0199] Table 10. Moving Die Rheology

[0200]

[0201] The compound properties of the uncured compounds are shown in Table 11. The compounds were cured using compression molding at 160°C for 8 minutes and the properties were evaluated as shown below. TM The tensile strength of the PEDM-based compounds (E3.1 to E3.3) showed a moderate decrease compared to the tensile strength of the control compound (C3.1) containing VISTALON 2502. The PEDM-based compound (E3.4) showed a decrease in tensile strength compared to the VISTALON 2502-containing TMThe control compound (C3.1) with VISTALON 2502 has a comparable tensile strength, which is higher than the PEDM-based compounds (E3.1, E3.2 and E3.3) and may come from the higher ENB% content of PEDM-2. The Die C tear strength of the PEDM-based compounds was found to be comparable to that of the compounds containing VISTALON TM The Die C tear strength of the control compound (C3.1) containing VISTALON 2502 was comparable. After aging at 150°C for 168 hours, the physical properties of the PEDM-based compounds (E3.1, E3.2, E3.3, and E3.4) showed comparable performance to those containing VISTALON TM The control compound (C3.1) of 2502 had comparable to higher retention.

[0202] Table 11. Compound properties

[0203]

[0204] Table 12 shows the picma viscosity, compression set and wear resistance of PEDM-based compounds (E3.1, E3.2, E3.3 and E3.4). The picma test properties were measured on the green compounds to evaluate the viscosity of the compounds of the present invention. Compared with the control compound (C3.1), the PEDM-based compounds (E3.1 and E3.4) showed higher viscosity, while the PEDM-based compounds (E3.2 and E3.3) showed comparable viscosity. The difference in viscosity of the PEDM compounds may come from the lower C2 content or MW of the PEDM-based compounds (E3.1 and E3.4) than the PEDM-based compounds (E3.2 and E3.3).

[0205] Regarding compression set (%), despite the lower ENB content of the PEDM grades like the PEDM-based compounds (E3.1, E3.2 and E3.3), the elastic properties of the PEDM-based compounds are comparable to the control compound (C3.1) at higher temperatures. At room temperature, the control compound (C3.1) shows better elastic properties than the PEDM-based compounds (E3.1, E3.2, E3.3 and E3.4).

[0206] The abrasion resistance of the PEDM based compounds (E3.1 to E3.4) is lower than that of the control compound (C3.1).

[0207] Table 12. Picma viscosity, compression set and wear resistance properties

[0208] Picma Viscosity Tester C3.1 E3.1 E3.2 E3.3 E3.4 Self-adhesiveness(kg) 0.97 1.30 1.02 0.89 1.25 Compression set Compression set (%) (25% / 72hr / RT) 14 26 25 26 27 Compression set (%) (25% / 72hr / 100℃) 52 57 61 52 50 Compression set (%) (25% / 72hr / 125℃) 68 73 72 65 69 Wear resistance (drum) <![CDATA[Wear loss (mm 3 )]]> 91 99 130 128 134

[0209] Table 13 shows the use of VISTALON TMTable 13 shows the properties of several additional blend compositions of 7001 and PEDM, whereby the PEDM polymer contains different ENB contents. PEDM polymers with different ENB contents were mixed with the same formulation and the properties are depicted in Table 13.

[0210] Table 13. Blend composition and conditions

[0211]

[0212]

[0213] The rheological properties of the PEDM-based compounds (E3.5-E3.8) are shown in Table 14. The Mooney viscosity of the compounds was found to be dependent on the Mooney viscosity of the polymer, the C3.2 content, and the ENB content compared to the control compounds (C3.3) and (C3.4). The PEDM-based compounds (E3.5, E3.6, and E3.7) showed lower Mooney viscosities when compared to the control compounds (C3.3) and (C3.4) and the PEDM-based compound (E3.8). The PEDM-based compound (E3.8) showed higher Mooney viscosity when compared to the control compounds (C3.3) and (C3.4). As for the scorch time of the compounds, the PEDM-based compound (E3.8) with a high ENB content showed lower scorch times (t5 and t35) when compared to the control compounds (C3.3) and (C3.4).

[0214] The MDR data show that the PEDM-based compounds with higher ENB content (e.g., E3.6, E3.7, and E3.8) show higher MH-ML, while the PEDM-based compound with lower ENB content (E3.5) shows lower MH-ML values ​​and thus lower crosslink density. In addition, the PEDM-based compounds with higher ENB content (E3.6 to E3.8) show lower cure time (tc90) values ​​when compared to the control compounds (C3.3) and (C3.4).

[0215] Table 14. Rheological properties

[0216]

[0217] Additional composition properties are shown in Table 15. The PEDM based compounds (E3.5 to E3.8) showed better tack when compared to the control compound (C3.3). The tack improvement ranged from 13% to 69% when compared to the EP(D)M formulation (C3.3), which is a very important property for multi-layer applications. It was also observed that the tensile properties improved with increasing ENB content when compared to the control compound (E3.5-E3.8).

[0218] Table 15. Composition properties

[0219]

[0220] Blend compositions including EP(D)M / PEDM (70:30) and EP(D)M / PEDM (30:70) were also prepared, characterized and evaluated as shown in Table 16. Higher blends of PEDM (70 phr) increased the tack properties. On the other hand, higher blends of PEDM (70 phr) reduced the Mooney viscosity and physical properties of the compounds. The PEDM-based compounds (E13 and E14) showed higher Picma viscosity values ​​than the control compound C4 containing phenolic resin. Therefore, the compositions of the present disclosure show better tack for multi-layer products such as conveyor belts, hoses, etc. Lower compound Mooney viscosity can improve calendering and extrusion.

[0221] Table 16. Blend composition and properties

[0222]

[0223]

[0224] All documents described herein, including any priority documents and / or test procedures are incorporated by reference in all jurisdictions not inconsistent with the present invention. It is apparent from the above overview and specific embodiments that, although some embodiments have been illustrated and described, various modifications can be made without departing from the spirit and scope of the present disclosure. Therefore, it is not desired that the present disclosure be limited in this manner. Likewise, the term "comprising" is considered synonymous with the term "including". Likewise, whenever a composition, element, or group of elements is preceded by the transitional term "comprising", it should be understood that the same composition or group of elements with the transitional term "essentially consisting of", "consisting of", "selected from", or "is" in front of the listed composition, element, or each element, and vice versa is also considered.

Claims

1. An elastomeric composition comprising: 5 parts per hundred parts by weight rubber (phr) to 80 phr of a propylene-alpha-olefin-diene (PEDM) terpolymer comprising 55 to 95 wt% propylene, 2.5 to 40 wt% alpha-olefin, and 0.05 to 25 wt% diene, the wt% being based on the weight of the PEDM terpolymer, wherein the PEDM terpolymer has a 125°C Mooney viscosity (ML(1+4)) of 5 MU to 90 MU and a weight average molecular weight of 120,000 to 320,000 g / mol; 20 to 95 phr of an ethylene-based copolymer selected from: (a) a crystalline ethylene-based copolymer comprising from 60 to 95 weight percent ethylene, from 0 to 10 weight percent of one or more dienes, and from 5 to 40 weight percent C3 to C12 alpha-olefins, the weight percents being based on the total weight of the crystalline ethylene-based copolymer, (b) an amorphous ethylene-based copolymer comprising from 40 wt% to 59 wt% ethylene, from 0 wt% to 10 wt% of one or more dienes, and from 40 wt% to 60 wt% C3 to C12 alpha-olefins, the wt% being based on the total weight of the amorphous ethylene-based copolymer, and (c) a combination of (a) and (b); and 10phr to 200phr of process oil.

2. The elastomeric composition of claim 1, comprising: 5phr to 50phr PEDM; 50 phr to 95 phr of an ethylene-based copolymer; and 10phr to 200phr of process oil.

3. The elastomeric composition of claim 2, wherein the composition has a raw rubber to rubber adhesion of 500 g-force / inch width or greater.

4. The elastomeric composition of claim 2, wherein the composition has a raw rubber to rubber adhesion of from 1000 g-force / inch-width to 5000 g-force / inch-width.

5. The elastomeric composition of claim 2, wherein the composition has a rubber-to-rubber adhesion after aging for 1 month at room temperature of 500 g-force / inch width or greater.

6. The elastomeric composition of claim 2, wherein the composition has a rubber-to-rubber adhesion after aging for 1 month at room temperature of 1000 g-force / inch-width or greater to 6000 g-force / inch-width.

7. The elastomeric composition of claim 2, wherein the composition has a raw rubber to rubber adhesion retention percentage from blending to aging for one month at room temperature of 50% to 250%.

8. The elastomeric composition of claim 2, wherein the composition has a raw rubber to rubber adhesion retention percentage from blending to aging for 1 month at room temperature of 100% to 250%.

9. Hose, including: Internal rubber tube; a reinforcing fabric surrounding the inner rubber tube; and a rubber layer surrounding the reinforcing fabric; Wherein the inner rubber tube and / or the rubber layer comprises the elastomeric composition according to one of claims 2 to 8.

10. The hose of claim 9, wherein the reinforcing fabric is selected from the group consisting of cotton, polyester, polyamide, acrylic, aramid, polyketone, hemp, jute, fiberglass, and any combination thereof.

11. The elastomeric composition of claim 1, comprising: 5 to 80 phr of said PEDM terpolymer; 20 phr to 95 phr of said crystalline ethylene-based copolymer; 0 to 75 phr of said amorphous ethylene-based copolymer; and 10phr to 30phr of process oil.

12. Belt, including: a first outer rubber layer; a second outer rubber layer; and a reinforcing fabric between said first and second outer rubber layers; Wherein the first outer rubber layer and / or the second outer rubber layer comprises the elastomeric composition of claim 11.

13. The belt of claim 12, wherein the reinforcing fabric is selected from the group consisting of: cotton, polyester, polyamide, acrylic, aramid, polyketone, hemp, jute, fiberglass, and any combination thereof.

14. Belt, including: a first outer rubber layer; a second outer rubber layer; and alternating layers of rubber skins and reinforcing fabrics between said first and second outer rubber layers; Wherein the first outer rubber layer and / or the second outer rubber layer and / or the rubber surface layer comprises the elastomer composition of claim 11.

15. The belt of claim 12, wherein the reinforcing fabric is selected from the group consisting of: cotton, polyester, polyamide, acrylic, aramid, polyketone, hemp, jute, fiberglass, and any combination thereof.

16. The elastomeric composition of any of the preceding claims, wherein the crystalline ethylene-based copolymer has a Mooney viscosity at 125°C (ML (1+4)) of 20 MU to 90 MU.

17. The elastomeric composition of any of the preceding claims, wherein the crystalline ethylene-based copolymer has a Hf of 15 J / g or greater.

18. The elastomeric composition of any of the preceding claims, wherein the amorphous ethylene-based copolymer has a Mooney viscosity at 125°C (ML (1+4)) of 20 MU to 90 MU.

19. The elastomeric composition of any of the preceding claims, wherein the amorphous ethylene-based copolymer has a Hf of 0 J / g to 14 J / g.

20. The elastomeric composition of any preceding claim, wherein the PEDM terpolymer has a number average molecular weight of from 50,000 g / mol to 150,000 g / mol.

21. The elastomeric composition of any preceding claim, wherein the PEDM terpolymer has a polydispersity index of from 2 to 2.

7.

22. The elastomeric composition of any preceding claim, further comprising from 1 phr to 500 phr of carbon black.

Citation Information

Patent Citations

  • Expansible thermoplastic polymer particles containing volatile fluid foaming agent and method of foaming the same

    US3615972A

  • Easy processing ethylene propylene elastomers

    US4722971A

  • Phenolic resin curatives which form nonstaining thermoplastic elastomers

    US5750625A

  • Process for producing objects

    US6582633B2

  • Multimodal ethylene-alpha-olefin elastomers and process for making

    US7915354B2